Method for manufacturing quantum dot light emitting diode

By using a zinc oxide electron transport layer in quantum dot light-emitting diodes and depositing amine or carboxyl ligands with 3-7 carbon atoms, the carrier injection balance is controlled, solving the problem of low lifetime of QLED devices and achieving high efficiency and long lifetime device performance.

CN114695748BActive Publication Date: 2026-11-06TCL TECHNOLOGY GROUP CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202011642134.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-31
Publication Date
2026-11-06
Estimated Expiration
2040-12-31

AI Technical Summary

Technical Problem

Existing quantum dot light-emitting diode devices have short lifespans, and existing improvement strategies based on OLED device theory cannot effectively improve the lifespan of QLED devices.

Method used

In quantum dot light-emitting diodes, an electron transport layer containing zinc oxide is used, and amine or carboxyl ligands with 3-7 carbon atoms are deposited on its surface. By reducing the amount of hydroxyl groups on the surface of zinc oxide nanoparticles through ligand exchange, the carrier injection balance is regulated, and a dynamic balance between electron injection rate and hole injection rate is achieved.

Benefits of technology

This improved the lifetime of quantum dot light-emitting diode devices while maintaining high external quantum efficiency, achieving a continuous balance of carrier injection and stable device performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114695748B_ABST
    Figure CN114695748B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of display, and provides a preparation method of a quantum dot light emitting diode. The quantum dot light emitting diode provided by the application comprises an anode and a cathode arranged oppositely, a quantum dot light emitting layer arranged between the anode and the cathode, and an electron transport layer arranged between the quantum dot light emitting layer and the cathode, wherein the electron transport layer comprises a first electron transport layer containing zinc oxide, and at least one side surface of the first electron transport layer contains an amine ligand and / or a carboxyl ligand with 3-7 carbon atoms; the preparation method of the first electron transport layer comprises the following steps: preparing a zinc oxide pre-prepared film on a pre-prepared device substrate to be prepared into the first electron transport layer; and after a solution of the amine ligand and / or the carboxyl ligand with 3-7 carbon atoms is deposited on the surface of the zinc oxide pre-prepared film, drying treatment is carried out to obtain a zinc oxide film. The preparation method of the quantum dot light emitting diode provided by the application effectively improves the service life of the quantum dot light emitting diode device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of display technology, and in particular relates to a method for preparing a quantum dot light-emitting diode. Background Technology

[0002] Quantum dots (QDs) are a class of nanomaterials composed of a small number of atoms. Their radii are typically smaller than or close to the exciton Bohr radius, exhibiting a significant quantum confinement effect and unique optical properties. Recently, with the continuous development of display technology, quantum dot light-emitting diodes (QLEDs), which use quantum dot materials as the light-emitting layer, have attracted increasing attention. QLEDs possess characteristics such as high luminous efficiency, controllable emission color, high color purity, good device stability, and applicability to flexible applications, showing great promise for use in display technology, solid-state lighting, and other fields.

[0003] QLEDs primarily consist of a cathode, an anode, and a quantum dot light-emitting layer. To improve device performance, QLEDs often incorporate one or more functional layers, such as a hole transport injection layer, a hole transport layer, an electron transport layer, and an electron injection layer. Zinc oxide, a commonly used electron transport layer material in QLEDs, exhibits excellent energy level matching with both the cathode and the quantum dot light-emitting layer, significantly reducing the injection barrier for electrons from the cathode to the quantum dot light-emitting layer. Furthermore, its deep valence band level effectively blocks holes. In addition, zinc oxide possesses excellent electron transport capabilities, with an electron mobility as high as 10⁻⁶. -3 cm 2 These properties make zinc oxide the preferred material for the electron transport layer in quantum dot light-emitting diode devices, significantly improving device stability and luminous efficiency.

[0004] Because QLED display technology and Organic Light-Emitting Diode (OLED) display technology share similarities in their light-emitting principles, the explanations of device physics, the selection of energy levels for functional layer materials, and the matching principles in QLED devices currently follow the existing theoretical framework of OLEDs. For example, in OLED devices, to achieve higher device performance, it is necessary to finely control the injection of charge carriers (holes and electrons) on both sides of the device to achieve a balance in carrier injection within the light-emitting layer. When applying these classical physics conclusions of OLED devices to the QLED device system, considering that the electron mobility of the zinc oxide layer is often higher than that of the hole transport layer, to achieve a better balance in carrier injection in QLED devices, it is necessary to reduce the electron mobility of the zinc oxide layer by inserting an electron blocking layer between the quantum dot light-emitting layer and the zinc oxide layer. When these methods are applied to QLED devices, the performance of QLED devices is indeed significantly improved, especially the efficiency. This method achieves an external quantum efficiency of over 20% for QLED devices, approaching the upper limit of the theoretical value.

[0005] However, attempts to improve and enhance another key performance characteristic of QLED devices—device lifetime—using the aforementioned strategies have encountered problems: the classic approaches and strategies developed for OLEDs have so far failed to effectively improve the lifetime of QLED devices. Furthermore, while high QLED device efficiencies have been achieved through these classic approaches and strategies, the lifetime of these highly efficient QLED devices is often significantly worse than that of similar devices with lower efficiencies. Simultaneously, with the gradual and in-depth research into the mechanisms of QLED devices, it has been discovered that due to the use of nanomaterials with special surface characteristics, such as quantum dots and ZnO nanoparticles, QLEDs possess unique mechanisms different from those of OLED devices. These mechanisms are closely related to the performance of QLED devices, especially their lifetime. Therefore, existing QLED device structures designed based on OLED device theory cannot meet the needs of improving QLED device performance, particularly lifetime. Corresponding to the unique device mechanisms of the QLED system, new and more targeted QLED device structures need to be developed. Summary of the Invention

[0006] The purpose of this application is to provide a method for fabricating quantum dot light-emitting diodes, which aims to solve the problem of short lifespan of existing quantum dot light-emitting diode devices.

[0007] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0008] This application provides a method for fabricating a quantum dot light-emitting diode (LED). The LED includes an anode and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The electron transport layer includes a first electron transport layer containing zinc oxide, and at least one surface of the first electron transport layer contains an amino ligand and / or a carboxyl ligand with 3-7 carbon atoms.

[0009] The method for preparing the first electron transport layer includes:

[0010] A zinc oxide pre-film is prepared on the pre-fabricated device substrate on which the first electron transport layer is to be prepared;

[0011] After depositing a solution of amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface of the zinc oxide pre-film, the film is dried to obtain a zinc oxide film.

[0012] The method for fabricating quantum dot light-emitting diodes provided in this application involves depositing a solution of amine and / or carboxyl ligands with 3-7 carbon atoms on the surface of a zinc oxide pre-film. This promotes ligand exchange between the amine and / or carboxyl ligands and the hydroxyl ligands on the surface of the zinc oxide colloid, thereby coordinating the amine and / or carboxyl ligands with 3-7 carbon atoms onto the surface of the zinc oxide colloid. Because the chain length of the coordinated amine and / or carboxyl ligands is relatively short, it does not significantly increase the distance between zinc oxide nanoparticles in the solution or after film formation. Simultaneously, it significantly reduces the amount of hydroxyl groups on the surface of the zinc oxide nanoparticles, thereby increasing the electron mobility of the zinc oxide electron transport layer after film formation and effectively improving the lifetime of the quantum dot light-emitting diode device. Attached Figure Description

[0013] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0014] Figure 1 This is a schematic diagram of the structure of an electronic transport layer provided in an embodiment of this application;

[0015] Figure 2 This is a schematic diagram of another electronic transport layer structure provided in an embodiment of this application;

[0016] Figure 3 This is a schematic diagram of the structure of the light-emitting diode provided in the embodiments of this application;

[0017] Figure 4This is a schematic diagram of the structure of a positive light-emitting diode provided in an embodiment of this application;

[0018] Figure 5 This is a schematic diagram of the structure of the inverted light-emitting diode provided in the embodiments of this application;

[0019] Figure 6 This is a flowchart of a first fabrication process for the first electron transport layer provided in an embodiment of this application;

[0020] Figure 7 This is a flowchart of a second fabrication process for the first electron transport layer provided in an embodiment of this application;

[0021] Figure 8 These are lifetime test results of quantum dot light-emitting diodes provided in Embodiment 1 and Comparative Example 1 of this application;

[0022] Figure 9 These are lifetime test results of quantum dot light-emitting diodes provided in Embodiment 2 and Comparative Example 1 of this application;

[0023] Figure 10 These are lifetime test results of quantum dot light-emitting diodes provided in Embodiment 3 and Comparative Example 1 of this application;

[0024] Figure 11 These are lifetime test results of quantum dot light-emitting diodes provided in Embodiment 4 and Comparative Example 1 of this application;

[0025] Figure 12 This is a schematic diagram illustrating the lifetime of a device provided in an embodiment of this application. Detailed Implementation

[0026] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0027] In the description of this application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0028] In quantum dot light-emitting diode (QD) devices, the electron mobility of the zinc oxide layer is often higher than that of the hole mobility of the hole transport layer. To achieve better carrier injection balance in QD devices, traditional methods involve inserting an electron blocking layer between the quantum dot emissive layer and the zinc oxide layer to reduce the electron mobility of the zinc oxide layer, thus balancing the injected electrons and holes in the quantum dot emissive layer. However, the low electron injection rate only achieves a momentary balance of charge injection during the initial operation of the QD device, resulting in high device efficiency at that initial stage. As the device continues to operate, the electron injection rate decreases continuously before the device reaches dynamic equilibrium, quickly disrupting this carrier injection balance. Consequently, the high device efficiency decreases and cannot be maintained. Furthermore, this carrier injection imbalance may worsen with continued operation, leading to a rapid decline in device lifetime.

[0029] In view of this, embodiments of this application provide a quantum dot light-emitting diode, including an anode and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode.

[0030] The electron transport layer contains zinc oxide, and at least a portion of the zinc oxide has an amino ligand and / or a carboxyl ligand with 3-7 carbon atoms on its surface.

[0031] The electron transport layer contains zinc oxide, and at least a portion of the zinc oxide surface contains amine ligands and / or carboxyl ligands with 3-7 carbon atoms. The introduction of amine and / or carboxyl ligands reduces the number of hydroxyl groups on the surface of the zinc oxide nanoparticles. Simultaneously, due to the short chain length of the coordinated amine / carboxyl ligands, the distance between the zinc oxide nanoparticles after film formation is not significantly increased, thus increasing the electron mobility of the zinc oxide electron transport layer. This results in more electrons being injected into the quantum dot emitting layer, making the electron-to-quantum-dot emitting layer injection rate higher than the hole-to-quantum-dot emitting layer injection rate. This situation causes the quantum dots in the emitting layer to become negatively charged. This negatively charged state is maintained by the binding effect of the quantum dot core-shell structure and the electrically inert surface ligands, while the Coulomb repulsion effect makes further electron injection into the quantum dot emitting layer increasingly difficult. When a quantum dot light-emitting diode (LED) device operates continuously until it reaches a stable state, the negatively charged state of the quantum dots also tends to stabilize. This means that the newly captured and bound electrons in the quantum dots reach a dynamic equilibrium with the electrons consumed by radiative transitions. The electron injection rate into the quantum dot light-emitting layer is much lower than in the initial stage. At this point, the lower electron injection rate and hole injection rate achieve a carrier injection balance, thus improving the device's lifetime. In other words, although the high electron injection rate initially causes an imbalance in carrier injection, affecting device performance, once the quantum dot LED device operates continuously until a stable state, the reduced electron injection rate balances with the hole injection rate, maintaining device efficiency and effectively extending the device's lifetime.

[0032] In this embodiment, the chain length, i.e., the number of carbon atoms, of the amino ligands and / or carboxyl ligands needs to be strictly controlled. When the chain length is too short, the acidity or basicity of the amino and / or carboxyl ligands will increase, causing an acid-base reaction with the zinc oxide nanoparticles after being added to the zinc oxide colloidal solution, affecting the quality of the final zinc oxide film. Conversely, when the chain length is too long, the steric hindrance effect will increase the distance between the zinc oxide nanoparticles in the film, thereby reducing the electron mobility of the zinc oxide electron transport layer, contrary to the original design purpose. For example, the amino and / or carboxyl ligands with 3-7 carbon atoms are selected from at least one of propionic acid, propylamine, butyric acid, butylamine, hexanoic acid, and hexylamine. In some embodiments, the amino and / or carboxyl ligands have 4-6 carbon atoms, thereby increasing the electron mobility of the electron transport layer while maintaining good film quality.

[0033] In some embodiments, the electron transport layer includes a first electron transport layer containing zinc oxide, and the surface of the zinc oxide forming the first electron transport layer contains amine ligands and / or carboxyl ligands with 3-7 carbon atoms. The introduction of amine ligands and / or carboxyl ligands can reduce the amount of hydroxyl groups on the surface of zinc oxide nanoparticles. At the same time, since the chain length of the coordinated amine / carboxyl ligands is relatively short, it does not increase the distance between zinc oxide nanoparticles after film formation, thereby increasing the electron mobility of the zinc oxide electron transport layer after film formation.

[0034] In some embodiments, in zinc oxide films containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on their surface, the molar ratio of the amine ligands and / or carboxyl ligands with 3-7 carbon atoms to zinc oxide is 1:4 to 4:1. In this case, the appropriate amount of amine ligands and / or carboxyl ligands on the surface of the zinc oxide nanoparticles can reduce the amount of hydroxyl groups on the surface of the zinc oxide nanoparticles, thereby increasing the electron mobility of the electron transport layer containing zinc oxide and thus improving the device lifetime of quantum dot light-emitting diodes. In some embodiments, the amine ligands and / or carboxyl ligands have 3-4 carbon atoms, and the molar ratio of the amine ligands and / or carboxyl ligands to zinc oxide nanoparticles is selected as 1:1 to 4:1; in some embodiments, the amine ligands and / or carboxyl ligands have 5-7 carbon atoms, and the molar ratio of the amine ligands and / or carboxyl ligands to zinc oxide nanoparticles is selected as 1:4 to 2:1. When the chain length is relatively long (5-7), the electron mobility of the sample will decrease after ligand exchange, similar to the effect of increasing the amount of hydroxyl groups. Therefore, the amount of ligands with longer chain lengths should not be too much. When the chain length is relatively short (3-4), the migration rate of the sample will increase after ligand exchange, similar to the effect of decreasing the amount of hydroxyl groups. Therefore, the amount of ligands with longer chain lengths can be increased.

[0035] In one possible implementation, the electron transport layer comprises only one thin film, which is the first electron transport layer. The material forming the electron transport layer is zinc oxide, and the surface of the zinc oxide contains amine ligands and / or carboxyl ligands with 3-7 carbon atoms. In this case, the electron transport resistance from the electron transport layer to the quantum dot emitting layer is low, which is beneficial for the quantum dots in the quantum dot emitting layer to become negatively charged. Bound by the quantum dot structure (quantum dot core-shell structure and electrically inert surface ligands), the negative dot state and Coulomb repulsion effect ensure that when the quantum dot emitting diode device continues to operate until a stable state is reached, the negatively charged state of the quantum dots also tends to stabilize. At this point, the electrons newly captured and bound by the quantum dots reach a dynamic equilibrium with the electrons consumed by radiative transitions. The electron injection rate to the quantum dot emitting layer is much lower than in the initial stage. This lower electron injection rate and hole injection rate achieve a carrier injection balance, thus improving the device lifetime.

[0036] In some embodiments, the zinc oxide in the first electron transport layer is undoped zinc oxide, meaning the electron transport layer is made of zinc oxide with amine ligands and / or carboxyl ligands containing 3-7 carbon atoms on its surface, and the zinc oxide does not contain any doped metals. It should be noted that the undoped zinc oxide film referred to in the embodiments of this application is a zinc oxide film relative to a metal-doped zinc oxide film, meaning that the zinc oxide forming the zinc oxide film is not doped with other metal ions. That is, the undoped zinc oxide film is a pure zinc oxide film.

[0037] In some embodiments, the zinc oxide in the first electron transport layer is metal-doped zinc oxide, that is, the zinc oxide in the electron transport layer is zinc oxide containing a doped metal. It should be understood that the doped metal referred to in this application refers to a metal ion other than zinc ions that is doped into zinc oxide in ionic form. When doped zinc oxide, obtained by doping zinc oxide with metal elements, is used as the electron transport layer material for quantum dot light-emitting diodes (LEDs), it is beneficial for achieving higher device efficiency in the LED device. However, the device lifetime is not ideal, and may even be worse than that of a quantum dot LED with an undoped pure zinc oxide electron transport layer. This is because the amount of hydroxyl groups on the surface of the doped zinc oxide electron transport layer changes along with the energy level / oxygen vacancy (electron mobility). Therefore, this embodiment achieves effective carrier injection control by binding amine ligands and / or carboxyl ligands with 3-7 carbon atoms to the surface of the metal-doped zinc oxide. Specifically, compared to adjusting the amount of hydroxyl groups on the surface of undoped zinc oxide films, adjusting the amount of hydroxyl groups on the surface of doped zinc oxide films has several advantages. First, through optimization of energy level matching or electron mobility in the doped zinc oxide, the quantum dot LED device is already in a better carrier injection equilibrium. In the initial stage of operation, it can achieve a higher external quantum efficiency (EQE) than quantum dot LED devices using undoped zinc oxide films as the electron transport layer. Second, because the doped zinc oxide film surface contains amine ligands and / or carboxyl ligands with 3-7 carbon atoms, the quantum dot LED device can also reach a carrier injection equilibrium state when it continues to operate until it reaches a stable state, thus achieving a good device lifetime. Ultimately, quantum dot LED devices can achieve improved lifetime while maintaining a high EQE.

[0038] In some embodiments, the dopant metal in metal-doped zinc oxide is selected from Mg. 2+ Mn 2+ At least one of the following. In this case, the doped metal ion and zinc ion have the same valence state, but their oxides are metal ions with different conduction band energy levels. In this case, doping with such a metal ion can adjust the conduction band energy level of the zinc oxide electron transport layer, thereby optimizing the energy level matching between the quantum dot light-emitting layer and the electron transport layer in the quantum dot light-emitting diode device and improving the EQE of the device.

[0039] In some embodiments, the dopant metal in metal-doped zinc oxide is selected from Al. 3+ Y 3+ La 3+ Li + Gd 3+ Zr 4+ Ce 4+ At least one of them. In this case, the doped metal ion is a metal ion with a different valence state than the zinc ion. By doping with this metal ion, the oxygen vacancies (electron mobility) in the zinc oxide electron transport layer can be adjusted, thereby optimizing the carrier injection balance of the QLED device and improving the EQE of the device.

[0040] The ionic radii of the doped metal ions differ from those of zinc ions, and their oxides also have different crystal structures (for example, MgO and MnO are NaCl-type cubic crystal systems, ZrO2 is a monoclinic crystal system, while ZnO is a wurtzite-type hexagonal crystal system). This results in a doping limit for the doped metal ions in zinc oxide materials. When the doping amount exceeds this limit, the doped metal ions will precipitate from the surface of the zinc oxide material as a second phase, thus adversely affecting the performance of the zinc oxide material. A comparison of the ionic radii of the doped metal ions and zinc ions provided in the embodiments of this application is shown in Table 1 below.

[0041] Table 1

[0042]

[0043] This application embodiment is based on the selected doped metal ion and Zn 2+ The difference in ionic radius can regulate the doping amount of the doped metal ion. The closer the ionic radius of the doped metal ion is to that of the zinc ion, and the more similar the crystal structures of their oxides, the higher the doping limit of the doped metal ion in zinc oxide materials. For example: when the doped metal is Mg... 2+ At that time, Mg in metal-doped zinc oxide 2+ The molar concentration of the doping is 0.1% to 35%; when the doped metal is Mn 2+ When Mn in metal-doped zinc oxide 2+ The molar concentration of the doping is 0.1% to 30%; when the doped metal is Al 3+ At that time, Al in metal-doped zinc oxide 3+ The molar concentration of the doping is 0.1% to 15%; when the doped metal is Y 3+ When Y is present in zinc oxide, it is a metal doped with zinc oxide. 3+ The molar concentration of the doping is 0.1% to 10%; when the doped metal is La 3+ When, La in metal-doped zinc oxide 3+The molar concentration of the doping is 0.1% to 7%; when the doping metal is Li + When Li in metal-doped zinc oxide + The molar concentration of the doping is 0.1% to 45%; when the doped metal is Gd 3+ At that time, Gd in metal-doped zinc oxide 3+ The molar concentration of the doping is 0.01% to 8%; when the doping metal is Zr 4+ When Zr in metal-doped zinc oxide 4+ The molar concentration of the doping is 0.1% to 45%; when the doped metal is Ce 4+ At that time, Ce in metal-doped zinc oxide 4+ The molar concentration of the dopant is 0.1% to 10%.

[0044] In some embodiments, when the electron transport layer is a first electron transport layer, the thickness of the first electron transport layer, i.e., the electron transport layer, is 10 to 100 nm.

[0045] In one possible implementation, the electron transport layer further includes a second electron transport layer, which is a zinc oxide film with a surface hydroxyl content greater than or equal to 0.6. That is, the electron transport layer simultaneously comprises a zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface and a zinc oxide film with a surface hydroxyl content greater than or equal to 0.6, both stacked along a direction perpendicular to the quantum dot light-emitting layer or cathode. In this scenario, when using a double-layer zinc oxide electron transport, the zinc oxide film with a high hydroxyl content on its surface reduces the number of electrons injected into the quantum dot emitting layer. This results in a lower electron injection efficiency in the initial stage of operation of the quantum dot emitting diode (LED), achieving carrier injection balance within the LED. The device remains in a state of equal carrier balance, thus exhibiting a higher external quantum efficiency. However, as the LED continues to operate until a stable state is reached, the presence of the zinc oxide film containing amine and / or carboxyl ligands ensures that the quantum dot emitting layer remains negatively charged, reaching a dynamic equilibrium. This results in a lower final electron injection efficiency, which, combined with the hole injection efficiency, forms a carrier injection balance. Consequently, the lifetime of the resulting quantum dot LED is also improved.

[0046] The first electron transport layer and the second electron transport layer are stacked, and their relative positions can be flexibly configured. In some embodiments, the second electron transport layer is disposed on the surface of the first electron transport layer near the cathode. In this case, when zinc oxide with a low surface hydroxyl content or a metal-doped zinc oxide colloidal solution is deposited on the quantum dot light-emitting layer, it is beneficial to obtain a smoother zinc oxide film. In some embodiments, the second electron transport layer may also be disposed on the surface of the first electron transport layer near the quantum dot light-emitting layer.

[0047] In some embodiments, both the first electron transport layer and the second electron transport layer are undoped zinc oxide films. That is, both the first and second electron transport layers are made of zinc oxide, which does not contain any doped metals, but the surface of the zinc oxide in the first electron transport layer contains amine ligands and / or carboxyl ligands with 3-7 carbon atoms. In some embodiments, the electron transport layer consists of a first electron transport layer containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface and a second electron transport layer with a surface hydroxyl content greater than or equal to 0.6.

[0048] In some embodiments, the zinc oxide in at least one of the first electron transport layer and the second electron transport layer is metal-doped zinc oxide.

[0049] In some embodiments, the zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms in the first electron transport layer is metal-doped zinc oxide, and the zinc oxide film with a surface hydroxyl content greater than or equal to 0.6, i.e., the second electron transport layer, is undoped zinc oxide. In this case, as mentioned above, on the one hand, the introduction of amine ligands and / or carboxyl ligands with 3-7 carbon atoms enables the quantum dot light-emitting diode device to reach a carrier injection equilibrium state even when it continues to operate to a steady state, thereby obtaining a good device lifetime. On the other hand, a high hydroxyl content can reduce the number of injected electrons in the quantum dot light-emitting layer, achieving carrier injection equilibrium in the quantum dot light-emitting diode device, ultimately resulting in a quantum dot light-emitting diode device with high external quantum efficiency. Furthermore, by doping zinc oxide with amine and / or carboxyl ligands having 3-7 carbon atoms, metal ions are incorporated to achieve effective carrier injection control. In the initial stage of device operation, a higher EQE can be obtained compared to quantum dot LEDs using undoped zinc oxide films as the electron transport layer. Additionally, the surface hydroxyl content of the second electron transport layer is greater than or equal to 0.6, and the synergistic effect further enhances the EQE of the quantum dot LED device. This embodiment achieves carrier injection balance in the QLED device simply by controlling the surface hydroxyl content of the zinc oxide film, without altering the device structure (inserting an electron blocking layer) or modifying the zinc oxide film through doping or other means. The entire process is simple, low-cost, and highly reproducible.

[0050] For example, the electron transport layer consists of a zinc oxide film (first electron transport layer) containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface and an undoped zinc oxide film (second electron transport layer) with a surface hydroxyl content greater than or equal to 0.6, and the zinc oxide in the first electron transport layer is metal-doped zinc oxide.

[0051] In some embodiments, the zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface, i.e., the first electron transport layer, is an undoped zinc oxide film, while the zinc oxide film with a surface hydroxyl content greater than or equal to 0.6, i.e., the second electron transport layer, is metal-doped zinc oxide. In this case, on the one hand, the introduction of amine ligands and / or carboxyl ligands with 3-7 carbon atoms reduces the amount of hydroxyl groups on the zinc oxide surface, enabling the quantum dot light-emitting diode device to reach a carrier injection equilibrium state even after continuous operation to a stable state, thereby achieving good device lifetime. On the other hand, a high hydroxyl content can reduce the number of injected electrons in the quantum dot light-emitting layer, achieving carrier injection equilibrium in the quantum dot light-emitting diode device, ultimately resulting in a quantum dot light-emitting diode device with high external quantum efficiency. Furthermore, by doping zinc oxide with a surface hydroxyl content greater than or equal to 0.6 with metal ions, effective carrier injection regulation can be achieved. In the early stages of device operation, a higher EQE can be obtained than that of quantum dot light-emitting diode devices with undoped zinc oxide film as the electron transport layer. In addition, the surface hydroxyl content of the second electron transport layer is greater than or equal to 0.6. The two work together to more effectively improve the EQE of quantum dot light-emitting diode devices.

[0052] For example, the electron transport layer consists of an undoped zinc oxide film (first electron transport layer) with amine ligands and / or carboxyl ligands having 3-7 carbon atoms and a zinc oxide film with a surface hydroxyl content greater than or equal to 0.6 (second electron transport layer), and the zinc oxide in the second electron transport layer is metal-doped zinc oxide.

[0053] In some embodiments, the zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms in the first electron transport layer is metal-doped zinc oxide, and the zinc oxide film with a surface hydroxyl content greater than or equal to 0.6 in the second electron transport layer is also metal-doped zinc oxide. In this case, on the one hand, the introduction of amine ligands and / or carboxyl ligands with 3-7 carbon atoms reduces the amount of hydroxyl groups on the zinc oxide surface, enabling the quantum dot light-emitting diode device to reach a carrier injection equilibrium state even after continuous operation to a stable state, thereby achieving good device lifetime. On the other hand, a high hydroxyl content can reduce the number of injected electrons in the quantum dot light-emitting layer, achieving carrier injection equilibrium in the quantum dot light-emitting diode device, ultimately resulting in a quantum dot light-emitting diode device with high external quantum efficiency. Furthermore, by doping zinc oxide with amine ligands and / or carboxyl ligands containing 3-7 carbon atoms and zinc oxide with a surface hydroxyl content of less than or equal to 0.4, metal ions are used to achieve effective carrier injection control. In the early stage of device operation, a higher EQE can be obtained than that of quantum dot light-emitting diode devices with undoped zinc oxide film as electron transport layer. In addition, the surface hydroxyl content of the second electron transport layer is greater than or equal to 0.6. The three factors work together to significantly improve the EQE of quantum dot light-emitting diode devices.

[0054] For example, the electron transport layer is composed of a zinc oxide film (first electron transport layer) containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface and a zinc oxide film (second electron transport layer) with a surface hydroxyl content greater than or equal to 0.6, and the zinc oxide in the first electron transport layer and the second electron transport layer are both metal-doped zinc oxide.

[0055] In one embodiment of the above embodiments, such as Figure 1 As shown, the electron transport layer 50 consists of a first electron transport layer 51 and a second electron transport layer 52, with the first electron transport layer 51 being closer to the quantum dot emitting layer 40 than the second electron transport layer 52, meaning the second electron transport layer 52 is closer to the cathode 60. When a zinc oxide colloidal solution containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms is deposited on the quantum dot emitting layer, it is beneficial to obtain a smoother zinc oxide film.

[0056] In some embodiments, the electron transport layer includes a first electron transport layer and a second electron transport layer. The second electron transport layer is disposed on the surface of the first electron transport layer near the cathode or the quantum dot light-emitting layer, and the second electron transport layer is a metal-doped zinc oxide thin film. In this case, the external quantum efficiency (EQE) of the quantum dot light-emitting diode is optimized directly by optimizing the energy level matching or electron mobility of the zinc oxide doping; by reducing the electron mobility of the first electron transport layer, the quantum dot light-emitting diode device can reach a carrier injection equilibrium state even when it continues to operate to a steady state, thereby obtaining a good device lifetime.

[0057] For example, such as Figure 1 As shown, the electron transport layer 50 includes a first electron transport layer 51 and a second electron transport layer 52. The second electron transport layer 52 is a metal-doped zinc oxide thin film, and it is disposed on the surface of the first electron transport layer 51 near the cathode 60, i.e., the first electron transport layer 51 is close to the quantum dot light-emitting layer 40. In this case, the external quantum efficiency (EQE) of the quantum dot light-emitting diode is optimized directly by optimizing the energy level matching or electron mobility of the zinc oxide doping. By reducing the electron mobility of the first electron transport layer, the quantum dot light-emitting diode device can reach a carrier injection equilibrium state even when it continues to operate to a stable state, thereby obtaining a good device lifetime. In addition, when the metal-doped zinc oxide colloidal solution is deposited on the quantum dot light-emitting layer, it is beneficial to obtain a more flat zinc oxide thin film.

[0058] In the above embodiments, when the electron transport layer is a double-layer zinc oxide thin film, the thickness of each zinc oxide thin film is 10-100 nm. In this case, the zinc oxide thin film thickness is suitable, making it less susceptible to electron breakdown, which is beneficial for maintaining the injection performance, film quality, and surface smoothness of the electron transport layer. Considering that zinc oxide thin films with a surface hydroxyl content greater than or equal to 0.6 or metal-doped zinc oxide thin films (second electron transport layer) have low electron mobility, the film thickness should not be too thick. For example, the thickness of zinc oxide thin films with a surface hydroxyl content greater than or equal to 0.6 or metal-doped zinc oxide thin films is 10-30 nm. Zinc oxide thin films or metal-doped zinc oxide thin films containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface (first electron transport layer) have higher electron mobility, so the film thickness can be appropriately thicker. For example, the thickness of zinc oxide thin films (first electron transport layer) containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface is 10-80 nm. The thickness of the metal-doped zinc oxide thin film is 20-60 nm.

[0059] In some embodiments of the above examples, the electron transport layer includes n thin-film stacked units composed of a first electron transport layer and a second electron transport layer, wherein n is greater than or equal to 2. Using a stacked electron transport layer may result in better energy level matching and a greater improvement in device lifetime. In some embodiments, n is an integer greater than or equal to 2 and less than or equal to 9.

[0060] In one possible implementation, the electron transport layer further includes a third electron transport layer. That is, the electron transport layer comprises a first electron transport layer with a surface hydroxyl content less than or equal to 0.4, a second electron transport layer, and a third electron transport layer. The second electron transport layer is a zinc oxide thin film or a metal-doped zinc oxide thin film with a surface hydroxyl content greater than or equal to 0.6.

[0061] In one embodiment, the third electron transport layer is a zinc oxide film with a surface hydroxyl content of less than or equal to 0.4.

[0062] In some embodiments, such as Figure 2As shown, the electron transport layer 50 includes a first electron transport layer 51 with amine ligands and / or carboxyl ligands having 3-7 carbon atoms on its surface, a second electron transport layer 52 with a surface hydroxyl content greater than or equal to 0.6, and a third electron transport layer 53 with a surface hydroxyl content less than or equal to 0.4. The third electron transport layer 53 is disposed on the side of the second electron transport layer 52 facing away from the first electron transport layer 51. In this configuration, a zinc oxide film with a low hydroxyl content and a zinc oxide film with amine ligands and / or carboxyl ligands having 3-7 carbon atoms on its surface enable the quantum dot light-emitting diode device to achieve carrier injection equilibrium even when continuously operating to a stable state, thus achieving good device lifetime. Conversely, a zinc oxide film with a high hydroxyl content can reduce the number of electrons injected into the quantum dot light-emitting layer, achieving carrier injection equilibrium in the quantum dot light-emitting diode device, ultimately resulting in a quantum dot light-emitting diode device with high external quantum efficiency. Furthermore, the deposition of zinc oxide with a low surface hydroxyl content or a zinc oxide-doped colloidal solution on the quantum dot light-emitting layer facilitates the formation of a smoother zinc oxide film. Thus, the resulting quantum dot light-emitting diode device has both good EQE and device lifetime.

[0063] In some embodiments, such as Figure 2As shown, the electron transport layer 50 includes a first electron transport layer 51 containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface, a metal-doped zinc oxide thin film (second electron transport layer 52), and a third electron transport layer 53 with a surface hydroxyl content of less than or equal to 0.4. The third electron transport layer 53 is disposed on the side of the second electron transport layer 52 facing away from the first electron transport layer 51. In this configuration, a zinc oxide thin film with a low hydroxyl content and a zinc oxide thin film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface enable the quantum dot light-emitting diode device to achieve carrier injection equilibrium even after continuous operation to a stable state, thus achieving good device lifetime. Conversely, a zinc oxide thin film with a high hydroxyl content reduces the number of electrons injected into the quantum dot light-emitting layer, achieving carrier injection equilibrium in the quantum dot light-emitting diode device, ultimately resulting in a quantum dot light-emitting diode device with high external quantum efficiency. Furthermore, the deposition of zinc oxide with a low surface hydroxyl content or a zinc oxide-doped colloidal solution on the quantum dot light-emitting layer facilitates the formation of a smoother zinc oxide thin film. Through energy level matching optimization or electron mobility optimization using zinc oxide doping, quantum dot light-emitting diode (LED) devices have achieved a superior carrier injection equilibrium. In the initial stage of operation, these devices exhibit a higher external quantum efficiency (EQE) compared to those using an undoped zinc oxide film as the electron transport layer. Furthermore, due to the low hydroxyl content on the surface of the zinc oxide doped film, the quantum dot LED devices can reach carrier injection equilibrium even after continuous operation to a stable state. This results in better device lifetime and maintains a high EQE during the initial operation phase.

[0064] In one embodiment, the third electron transport layer is a zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface.

[0065] In some embodiments, such as Figure 2As shown, the electron transport layer 50 includes a first electron transport layer 51 with amine ligands and / or carboxyl ligands having 3-7 carbon atoms on its surface, a second electron transport layer 52 with a hydroxyl content greater than or equal to 0.6, and a third electron transport layer 53 with amine ligands and / or carboxyl ligands having 3-7 carbon atoms on its surface. The third electron transport layer 53 is disposed on the side of the second electron transport layer 52 facing away from the first electron transport layer 51. In this configuration, the two zinc oxide films with amine ligands and / or carboxyl ligands having 3-7 carbon atoms on their surfaces enable the quantum dot light-emitting diode device to achieve carrier injection equilibrium even when continuously operating to a stable state, thus achieving good device lifetime. Furthermore, the zinc oxide film with a high hydroxyl content reduces the number of electrons injected into the quantum dot light-emitting layer, achieving carrier injection equilibrium in the quantum dot light-emitting diode device, ultimately resulting in a quantum dot light-emitting diode device with high external quantum efficiency. Furthermore, the deposition of zinc oxide with a lower surface hydroxyl content or a zinc oxide-doped colloidal solution on the quantum dot light-emitting layer facilitates the formation of a smoother zinc oxide film. Consequently, the resulting quantum dot light-emitting diode device exhibits both excellent EQE and device lifetime.

[0066] In some embodiments, such as Figure 2 As shown, the electron transport layer 50 includes a first electron transport layer 51 with amine ligands and / or carboxyl ligands having 3-7 carbon atoms on its surface, a metal-doped zinc oxide thin film (second electron transport layer 52), and a third electron transport layer 53 with amine ligands and / or carboxyl ligands having 3-7 carbon atoms on its surface, wherein the third electron transport layer 53 is disposed on the side of the second electron transport layer 52 facing away from the first electron transport layer 51. In this configuration, the two zinc oxide films containing 3-7 carbon atoms of amine and / or carboxyl ligands on their surfaces enable the quantum dot LED device to reach carrier injection equilibrium even after continuous operation to a steady state, thus achieving good device lifetime. Furthermore, through energy level matching optimization or electron mobility optimization via zinc oxide doping, the quantum dot LED device is already in a superior carrier injection equilibrium, resulting in a higher external quantum efficiency (EQE) in the initial stages of operation compared to quantum dot LEDs using undoped zinc oxide films as the electron transport layer. Moreover, the low hydroxyl content on the surface of the zinc oxide-doped film allows the quantum dot LED device to reach carrier injection equilibrium even after continuous operation to a steady state. This leads to better device lifetime and a higher EQE in the initial stages of operation.

[0067] In one embodiment, the third electron transport layer is a zinc oxide film with a surface hydroxyl content greater than or equal to 0.6.

[0068] In some embodiments, the electron transport layer comprises a first electron transport layer containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface, a second electron transport layer with a surface hydroxyl content greater than or equal to 0.6, and a third electron transport layer with a surface hydroxyl content greater than or equal to 0.6, wherein the third electron transport layer is disposed on the surface of the first electron transport layer opposite to the second electron transport layer. In this case, the zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface enables the quantum dot light-emitting diode device to reach a carrier injection equilibrium state even when it continues to operate to a stable state, thereby obtaining a good device lifetime; while the two zinc oxide films with high hydroxyl content can reduce the injected electrons in the quantum dot light-emitting layer, achieving carrier injection equilibrium in the quantum dot light-emitting diode device, ultimately resulting in a quantum dot light-emitting diode device with high external quantum efficiency. In addition, the deposition of zinc oxide with a lower surface hydroxyl content or a zinc oxide-doped colloidal solution on the quantum dot light-emitting layer is beneficial for obtaining a more flat zinc oxide film. Thus, the resulting quantum dot light-emitting diode device has both good EQE and device lifetime.

[0069] In some embodiments, the electron transport layer comprises a first electron transport layer containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface, a metal-doped zinc oxide film (second electron transport layer), and a third electron transport layer with a surface hydroxyl content greater than or equal to 0.6, wherein the third electron transport layer is disposed on the side of the first electron transport layer facing away from the second electron transport layer. In this case, the zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface enables the quantum dot light-emitting diode device to achieve a carrier injection equilibrium state even when it continues to operate to a stable state, thereby obtaining a good device lifetime; while the two zinc oxide films with high hydroxyl content can reduce the injected electrons in the quantum dot light-emitting layer, achieve carrier injection equilibrium in the quantum dot light-emitting diode device, and ultimately obtain a quantum dot light-emitting diode device with high external quantum efficiency. By optimizing energy level matching or electron mobility through zinc oxide doping, quantum dot LED devices are already in a superior carrier injection equilibrium state. In the initial stage of operation, they achieve a higher external quantum efficiency (EQE) than quantum dot LEDs using undoped zinc oxide films as the electron transport layer. Furthermore, due to the low hydroxyl content on the surface of the zinc oxide-doped film, the quantum dot LED devices can also reach carrier injection equilibrium even after continuous operation to a steady state. This results in better device lifetime and maintains a high EQE in the early stages of operation.

[0070] In some embodiments, the third electron transport layer is a metal-doped zinc oxide thin film.

[0071] In some embodiments, the electron transport layer comprises a first electron transport layer containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on its surface, a metal-doped zinc oxide film (second electron transport layer), and a metal-doped zinc oxide film (third electron transport layer), with the third electron transport layer disposed on the side of the first electron transport layer facing away from the second electron transport layer. In this case, the two zinc oxide films containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on their surfaces enable the quantum dot light-emitting diode device to reach a carrier injection equilibrium state even after continuous operation to a stable state, thereby achieving good device lifetime. Furthermore, through energy level matching optimization or electron mobility optimization of the zinc oxide doping, the quantum dot light-emitting diode device is already in a better carrier injection equilibrium state, and can achieve a higher external quantum efficiency (EQE) in the early stages of device operation compared to quantum dot light-emitting diode devices without zinc oxide film as the electron transport layer. Due to the low hydroxyl content on the surface of the zinc oxide doping film, the quantum dot light-emitting diode device can also reach a carrier injection equilibrium state even after continuous operation to a stable state. This allows quantum dot LEDs to achieve better device lifespan and maintain a higher EQE in the early stages of operation.

[0072] It should be understood that in embodiments where the electron transport layer contains a third electron transport layer, the zinc oxide film with a surface hydroxyl content of less than or equal to 0.4 can be an undoped zinc oxide film or a metal-doped zinc oxide film; similarly, the zinc oxide film with a surface hydroxyl content of greater than or equal to 0.6 can be an undoped zinc oxide film or a metal-doped zinc oxide film.

[0073] In embodiments where the electron transport layer includes a third electron transport layer, the thickness of the electron transport layer is 10–100 nm in some embodiments. In some embodiments, the thickness of the zinc oxide film containing amine ligands and / or carboxyl ligands with 3–7 carbon atoms on its surface is 10–80 nm. In some embodiments, the thickness of the zinc oxide film with a surface hydroxyl content of less than or equal to 0.4 is 20–60 nm. In some embodiments, the thickness of the zinc oxide film with a surface hydroxyl content of greater than or equal to 0.6 is 10–30 nm. In some embodiments, the thickness of the metal-doped zinc oxide film is 10–30 nm. Since the second electron transport layer is a zinc oxide film with a surface hydroxyl content of greater than or equal to 0.6 or a metal-doped zinc oxide film, the thickness of the second electron transport layer is 10–30 nm. The thickness of each layer is within this range, making the zinc oxide film thickness suitable in this case, less susceptible to electron breakdown, and beneficial for maintaining the injection performance, film quality, and surface smoothness of the electron transport layer. In particular, zinc oxide films with a surface hydroxyl content greater than or equal to 0.6 or metal-doped zinc oxide films have relatively thinner film thicknesses due to their lower electron mobility; zinc oxide films containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface, or zinc oxide films with a surface hydroxyl content less than or equal to 0.4, have relatively thicker film thicknesses due to their higher electron mobility.

[0074] In embodiments where the electron transport layer includes a second electron transport layer, and the second electron transport layer is a metal-doped zinc oxide thin film, and in embodiments where the electron transport layer includes a second electron transport layer and a third electron transport layer, and the second electron transport layer and / or the third electron transport layer is a metal-doped zinc oxide thin film, the type of doped metal in the metal-doped zinc oxide thin film, the effect of the doped metal, and the doping content of the doped metal are as described above (in the case where the electron transport layer is the first electron transport layer), and will not be repeated here for the sake of brevity.

[0075] In some embodiments, the dopant metal in the metal-doped zinc oxide thin film is selected from Mg. 2+ Mn 2+ At least one of the following. In some embodiments, the dopant metal in the metal-doped zinc oxide thin film is selected from Al. 3+ Y 3+ La 3+ Li + Gd 3+ Zr 4+ Ce 4+ At least one of them.

[0076] In some embodiments, when the doped metal is Mg 2+ At that time, Mg in metal-doped zinc oxide thin films 2+ The molar concentration of the doping is 0.1% to 35%; when the doped metal is Mn2+ When Mn in metal-doped zinc oxide thin films 2+ The molar concentration of the doping is 0.1% to 30%; when the doped metal is Al 3+ At that time, Al in metal-doped zinc oxide thin films 3+ The molar concentration of the doping is 0.1% to 15%; when the doped metal is Y 3+ At that time, Y in metal-doped zinc oxide thin films 3+ The molar concentration of the doping is 0.1% to 10%; when the doped metal is La 3+ At that time, La in metal-doped zinc oxide thin films 3+ The molar concentration of the doping is 0.1% to 7%; when the doping metal is Li + At that time, Li in metal-doped zinc oxide thin films + The molar concentration of the doping is 0.1% to 45%; when the doped metal is Gd 3+ At that time, Gd in metal-doped zinc oxide thin films 3+ The molar concentration of the doping is 0.01% to 8%; when the doping metal is Zr 4+ At that time, Zr in metal-doped zinc oxide thin films 4+ The molar concentration of the doping is 0.1% to 45%; when the doped metal is Ce 4+ At that time, Ce in metal-doped zinc oxide thin films 4+ The molar concentration of the dopant is 0.1% to 10%.

[0077] In some embodiments, such as Figure 3 As shown, the quantum dot light-emitting diode includes an anode 10 and a cathode 60 disposed opposite to each other, and a quantum dot light-emitting layer 40 disposed between the cathode 60 and the anode 10. An electron transport layer 50 is disposed between the cathode 60 and the quantum dot light-emitting layer 40.

[0078] In some embodiments, the light-emitting diode further includes a hole functional layer disposed between the anode 10 and the quantum dot light-emitting layer 40. The hole functional layer includes at least one of a hole transport layer, a hole injection layer, and an electron blocking layer. In some embodiments, the quantum dot light-emitting diode further includes an electron injection layer disposed between the cathode 60 and the electron transport layer 50.

[0079] In the above embodiments, the light-emitting diode may further include a substrate, with the anode 10 or the cathode 60 disposed on the substrate.

[0080] The light-emitting diodes provided in this application are divided into upright light-emitting diodes and inverted light-emitting diodes.

[0081] In one embodiment, a positive quantum dot light-emitting diode includes an anode 10 and a cathode 60 disposed opposite to each other, a quantum dot light-emitting layer 40 disposed between the anode 10 and the cathode 60, and an electron transport layer 50 disposed between the cathode 60 and the quantum dot light-emitting layer 40, wherein the anode 10 is disposed on a substrate. In some embodiments, a hole transport layer 30 is disposed between the anode 10 and the quantum dot light-emitting layer 40; further, a hole injection layer 20 is disposed between the anode 10 and the hole transport layer; and / or, an electron injection layer is disposed between the cathode 60 and the electron transport layer 50. In some embodiments of positive light-emitting diodes, such as... Figure 4 As shown, the quantum dot light-emitting diode includes a substrate 100, an anode 10 disposed on the surface of the substrate 100, a hole injection layer 20 disposed on the surface of the anode 10, a hole transport layer disposed on the surface of the hole injection layer 20, a quantum dot light-emitting layer 40 disposed on the surface of the hole transport layer, an electron transport layer 50 disposed on the surface of the quantum dot light-emitting layer 40, and a cathode 60 disposed on the surface of the electron transport layer 50.

[0082] In one embodiment, the inverted quantum dot light-emitting diode includes a stacked structure comprising an anode 10 and a cathode 60 disposed opposite to each other, a quantum dot light-emitting layer 40 disposed between the anode 10 and the cathode 60, and an electron transport layer 50 disposed between the cathode 60 and the quantum dot light-emitting layer 40, wherein the cathode 60 is disposed on a substrate. In some embodiments, a hole transport layer 30 is disposed between the anode 10 and the quantum dot light-emitting layer 40; further, a hole injection layer 20 is disposed between the anode 10 and the hole transport layer; and / or, an electron injection layer is disposed between the cathode 60 and the electron transport layer 50. In some embodiments of the inverted light-emitting diode, such as Figure 5 As shown, the quantum dot light-emitting diode includes a substrate 100, a cathode 60 disposed on the surface of the substrate 100, an electron transport layer 50 disposed on the surface of the cathode 60, a light-emitting layer 40 disposed on the surface of the electron transport layer 50, a hole transport layer disposed on the surface of the quantum dot light-emitting layer 40, a hole injection layer 20 disposed on the surface of the hole transport layer, and an anode 10 disposed on the surface of the hole injection layer 20.

[0083] In the above embodiments, the substrate 100 may be a rigid substrate or a flexible substrate, specifically selected from glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyethersulfone, or a combination formed of at least two of the above materials, or a laminated structure formed of at least two of the above materials.

[0084] In some embodiments, the material of the hole injection layer 20 may be at least one of poly(ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS), HTL-1, and HTL-2. Of course, it may also be other hole injection materials with high injection performance.

[0085] The structure of PEDOT:PSS is as follows:

[0086] The structure of HTL-1 is as follows:

[0087] The structure of HTL-2 is as follows:

[0088] In some embodiments, the material of the hole transport layer 30 may be selected from conventional hole transport materials. Exemplarily, the material of the hole transport layer 30 includes at least one of 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB), poly(4-butylphenyl-diphenylamine) (poly-TPD), 4,4',4'-tris(N-carbazolyl)-triphenylamine (TCTA), poly(N-vinylcarbazole) (PVK), and their derivatives. Of course, the material of the hole transport layer 30 may also be other hole transport materials with high injection performance.

[0089] The quantum dot emitting layer 40 contains quantum dots of one of three types: red, green, and blue, and can also contain yellow quantum dots. The quantum dots may or may not contain cadmium. In some embodiments, the quantum dots in the quantum dot emitting layer 40 can be mononuclear quantum dots or core-shell structured quantum dots. The core and shell compounds of the quantum dots can be independently selected from at least one of CdS, CdSe, CdTe, ZnO, ZnS, ZnSe, ZnTe, GaAs, GaP, GaSb, HgS, HgSe, HgTe, InAs, InP, InSb, AlAs, AlP, CuInS, CuInSe, and various core-shell or alloy structured quantum dots. The resulting quantum dot emitting layer exhibits a broad and continuously distributed excitation spectrum and high emission spectrum stability.

[0090] In this embodiment, the material and thickness of the electron transport layer 50 are as described above and will not be repeated here. In this embodiment, the thickness of the electron transport layer is 10–100 nm. When the thickness of the electron transport layer is less than 10 nm, the film layer is easily broken down by electrons, making it difficult to guarantee the carrier injection performance; when the thickness of the electron transport layer is greater than 100 nm, it will hinder electron injection and affect the charge injection balance of the device.

[0091] The bottom electrode (anode 10 bonded to substrate 100 or cathode 60 bonded to substrate 100) may be made of common bottom electrode materials. In some embodiments, the bottom electrode material includes at least one of zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), and fluorine-doped tin oxide.

[0092] In some embodiments, the top electrode (anode 10 or cathode 60 away from substrate 100) is a transparent oxide, a thin metal, or a combination of both. In some embodiments, the transparent oxide may be ITO, IZO, or AZO; in some embodiments, the thin metal may be Ag, Al, Au, Mg, Ca, Yb, Ba, or alloys thereof; in some embodiments, the top electrode may also be O / M / O, where M is Ag, Al, Au, Mg, Ca, Yb, Ba, or alloys thereof, and O is an oxide, including but not limited to ITO, IZO, and AZO.

[0093] The quantum dot light-emitting diode provided in this application embodiment contains zinc oxide in its electron transport layer, and at least a portion of the zinc oxide surface contains amine ligands and / or carboxyl ligands with 3-7 carbon atoms. The introduction of amine and / or carboxyl ligands reduces the amount of hydroxyl groups on the surface of the zinc oxide nanoparticles. Simultaneously, because the chain length of the coordinated amine / carboxyl ligands is relatively short, it does not increase the distance between the zinc oxide nanoparticles after film formation, thereby increasing the electron mobility of the zinc oxide electron transport layer after film formation. This results in more electrons being injected into the quantum dot light-emitting layer, making the electron injection rate into the quantum dot light-emitting layer higher than the hole injection rate. This situation causes the quantum dots in the quantum dot light-emitting layer to become negatively charged. This negatively charged state is maintained by the binding effect of the quantum dot core-shell structure and the electrically inert surface ligands, while the Coulomb repulsion effect makes further electron injection into the quantum dot light-emitting layer increasingly difficult. When a quantum dot light-emitting diode (LED) device operates continuously until it reaches a stable state, the negatively charged state of the quantum dots also tends to stabilize. This means that the newly captured and bound electrons in the quantum dots reach a dynamic equilibrium with the electrons consumed by radiative transitions. The electron injection rate into the quantum dot light-emitting layer is much lower than in the initial stage. At this point, the lower electron injection rate and hole injection rate achieve a carrier injection balance, thus improving the device's lifetime. In other words, although the high electron injection rate initially causes an imbalance in carrier injection, affecting device performance, once the quantum dot LED device operates continuously until a stable state, the reduced electron injection rate balances with the hole injection rate, maintaining device efficiency and effectively extending the device's lifetime.

[0094] It should be noted that in the embodiments of this application, the amount of hydroxyl groups on the surface of the zinc oxide film is determined by X-ray photoelectron spectroscopy (XPS). Specifically, in the X-ray photoelectron spectroscopy (XPS) detection results, the O1s spectrum can be divided into three sub-peaks: the OM peak (located between 529 eV and 531 eV), representing the molar concentration of oxygen atoms in the zinc oxide crystal; the OV peak (located between 531 eV and 532 eV), representing the molar concentration of oxygen vacancies in the zinc oxide crystal; and the OH peak (located between 532 eV and 534 eV), representing the molar concentration of hydroxyl ligands on the surface of the zinc oxide crystal. The area ratio between each sub-peak represents the ratio of the molar concentrations of different types of oxygen atoms in the zinc oxide film. Therefore, the amount of hydroxyl groups on the surface of the zinc oxide film is defined as: the area of ​​the OH peak / the area of ​​the OM peak, that is, the amount of hydroxyl groups on the surface of the zinc oxide film is the ratio of the molar concentration of hydroxyl ligands on the surface of the zinc oxide film to the molar concentration of oxygen atoms in the zinc oxide crystal.

[0095] The quantum dot light-emitting diodes provided in this application can be prepared by various methods. Below, this application provides two examples of methods for preparing the aforementioned quantum dot light-emitting diodes.

[0096] In a first embodiment, this application provides a method for fabricating a quantum dot light-emitting diode (LED). The quantum dot LED includes an anode and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The electron transport layer includes a first electron transport layer containing zinc oxide, and the surface of the zinc oxide forming the first electron transport layer contains amine ligands and / or carboxyl ligands with 3-7 carbon atoms.

[0097] Among them, such as Figure 6 As shown, the method for preparing the first electron transport layer is as follows:

[0098] S11. A zinc oxide colloidal solution is prepared by solution method using zinc salt solution, alkaline solution and amine ligands and / or carboxyl ligands with 3-7 carbon atoms as raw materials; wherein the zinc oxide surface in the zinc oxide solution is bound with amine ligands and / or carboxyl ligands with 3-7 carbon atoms;

[0099] S12. A zinc oxide colloidal solution is formed on the prefabricated device substrate on which the first electron transport layer is to be prepared, and the solvent is removed to obtain the first electron transport layer.

[0100] The quantum dot light-emitting diode fabrication method provided in this application involves adding amine ligands and / or carboxyl ligands with 3-7 carbon atoms during the synthesis of a zinc oxide colloidal solution. This promotes ligand exchange between the amine ligands and / or carboxyl ligands and the hydroxyl ligands on the surface of the zinc oxide colloid, thereby coordinating the amine ligands and / or carboxyl ligands with 3-7 carbon atoms onto the surface of the zinc oxide colloid. Because the chain length of the coordinated amine ligands and / or carboxyl ligands is relatively short, it does not significantly increase the distance between zinc oxide nanoparticles in the solution or after film formation. Simultaneously, it reduces the amount of hydroxyl groups on the surface of the zinc oxide nanoparticles, thereby increasing the electron mobility of the zinc oxide electron transport layer after film formation and effectively improving the lifetime of the quantum dot light-emitting diode device.

[0101] In the embodiments of this application, the composition of the quantum dot light-emitting diode, particularly the electron transport layer, the selection of amine ligands and / or carboxyl ligands with 3-7 carbon atoms, and the thickness of the zinc oxide film containing amine ligands and / or carboxyl ligands with 3-7 carbon atoms, are as described in the first aspect above, and will not be repeated here for the sake of brevity.

[0102] In step S11 above, the basic process for preparing zinc oxide using the solution method is as follows: a zinc salt solution is mixed with an alkaline solution to react and generate a hydroxide intermediate, such as zinc hydroxide; the hydroxide intermediate undergoes a condensation reaction to gradually generate zinc oxide nanoparticles. Based on this, in this embodiment, during the synthesis of the zinc oxide colloidal solution, an amino ligand and / or carboxyl ligand with a chain length of 3-7 carbons is added. This allows ligand exchange between the amino and / or carboxyl ligands and the hydroxyl ligands on the surface of the zinc oxide colloid, thereby coordinating the 3-7 carbon amino and / or carboxyl ligands onto the surface of the zinc oxide colloid. Since the coordinated amino and / or carboxyl ligands have relatively short chain lengths, they do not significantly increase the distance between zinc oxide nanoparticles in the solution or after film formation. Simultaneously, they reduce the amount of hydroxyl groups on the surface of the zinc oxide nanoparticles, thereby increasing the electron mobility of the zinc oxide film after film formation. This effectively achieves the same effect as having a hydroxyl group content on the zinc oxide film surface of less than or equal to 0.4.

[0103] In the method of preparing zinc oxide colloidal solution by solution method using zinc salt solution, alkaline solution and amine ligands and / or carboxyl ligands with 3-7 carbon atoms as raw materials, there are multiple time points for adding amine ligands and / or carboxyl ligands with 3-7 carbon atoms, and there are several corresponding ways to prepare zinc oxide colloidal solution by solution method.

[0104] In the first implementation, an amine ligand with 3-7 carbon atoms and / or a carboxyl ligand are added in the early stage of zinc oxide colloidal solution synthesis. That is, an amine ligand with 3-7 carbon atoms and / or a carboxyl ligand are added to the zinc salt solution at the same time as the alkali solution.

[0105] At this point, the steps for preparing zinc oxide colloidal solution by solution method include:

[0106] Zinc oxide nanoparticles with 3-7 carbon atoms bonded to their surface are prepared by mixing and reacting zinc salt solution, alkaline solution, and amine ligands and / or carboxyl ligands with 3-7 carbon atoms.

[0107] Zinc oxide nanoparticles were dissolved to obtain a zinc oxide colloidal solution.

[0108] In the above steps, the zinc salt solution is a salt solution formed by dissolving zinc salt in a solvent. The zinc salt is selected from those capable of reacting with alkaline solutions to form zinc hydroxide, including but not limited to zinc acetate, zinc nitrate, zinc sulfate, and zinc chloride. The solvent is selected from solvents that are soluble in zinc salts, including but not limited to highly polar solvents such as water, organic alcohols, organic ethers, and sulfones. In some embodiments, the solvent is selected from at least one of water, organic alcohols, organic ethers, and sulfones. These solvents have good solubility in zinc salts, are relatively stable as reaction media in alkaline environments, and are less likely to introduce side reactions. For example, the solvent may be selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and dimethyl sulfoxide (DMSO).

[0109] In this embodiment, the alkaline solution is a solution formed by an alkali capable of reacting with zinc salts to generate zinc hydroxide. The alkaline solution is obtained by dissolving or diluting with a solvent. The alkali in the alkaline solution can be either an inorganic or organic alkali. In one possible embodiment, the alkali in the alkaline solution is an inorganic alkali; for example, the inorganic alkali is selected from at least one of potassium hydroxide, sodium hydroxide, and lithium hydroxide. In another possible embodiment, the alkali in the alkaline solution is an organic alkali; for example, the weak alkali is selected from at least one of TMAH, ammonia, ethanolamine, and ethylenediamine. In some embodiments, the solvent used to dissolve or dilute the alkali to form the alkaline solution can be the same as or different from the solvent in the zinc salt solution. In some embodiments, selecting the same solvent as the zinc salt solution is more beneficial for obtaining a stable reaction system. The same solvent includes, but is not limited to, highly polar solvents such as water, organic alcohols, organic ethers, and sulfones. In some embodiments, the solvent is selected from at least one of water, organic alcohols, organic ethers, and sulfones. For example, the solvent may be selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and dimethyl sulfoxide (DMSO).

[0110] In some embodiments, the amine ligands and / or carboxyl ligands having 3-7 carbon atoms include, but are not limited to, propionic acid, propylamine, butyric acid, butylamine, hexanoic acid, and hexylamine. In some embodiments, the amine ligands and / or carboxyl ligands having 3-7 carbon atoms are prepared into a ligand solution and then reacted with a zinc salt solution and an alkaline solution. The solvent in the ligand solution is selected from solvents with high polarity, mainly considering the solubility of the reactants and products. For example, the solvent in the ligand solution is selected from at least one of methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO. In some embodiments, the amine ligands and / or carboxyl ligands having 3-7 carbon atoms are used as the ligand solution, and the concentration of the ligand solution is 0.2-0.4 mmol / L. When the ligand concentration is too low, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is too small, making it difficult to achieve effective ligand exchange. When the ligand concentration is too high, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is too large, and a large amount of ligands remaining in the solution will remain in the first electron transport layer, affecting the film formation quality and properties of the electron transport layer.

[0111] In some embodiments, the amount of alkali added satisfies the following condition: the molar ratio of hydroxide ions provided by the alkali to zinc ions provided by the zinc salt is 1.5:1 to 2.5:1, to ensure the formation of zinc oxide nanoparticles and reduce the generation of reaction byproducts. When the molar ratio of hydroxide ions to zinc ions is less than 1.5:1, the zinc salt is significantly in excess, making it difficult for a large amount of zinc salt to form zinc oxide nanoparticles; while when the molar ratio of hydroxide ions to zinc ions is greater than 2.5:1, the alkali is significantly in excess, and the excess hydroxide ions form a stable complex with the zinc hydroxide intermediate, making it difficult to condense and form zinc oxide nanoparticles. In some embodiments, in the step of mixing the zinc salt solution with the alkali, the amount of zinc salt solution and alkali added satisfies the following condition: the molar ratio of hydroxide ions provided by the alkali to zinc ions provided by the zinc salt is 1.7:1 to 1.9:1.

[0112] In some embodiments, the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms added satisfies the following condition: the molar ratio of the amine ligands and / or carboxyl ligands with 3-7 carbon atoms to the zinc salt in the zinc salt solution is 1:1 to 10:1. In this case, the added amine ligands and / or carboxyl ligands with 3-7 carbon atoms bind to the surface of the generated zinc oxide nanoparticles, reducing the number of hydroxyl ligands on the surface of the zinc oxide nanoparticles, thereby improving the lifespan of the device. However, if the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms is too large, too many ligands will be attached to the zinc oxide surface, reducing the electron mobility of zinc oxide and hindering the achievement of long-life devices; while if the amount of ligands is too small, too few ligands will be attached to the zinc oxide surface, making it difficult to reduce the amount of surface hydroxyl ligands, and also making it difficult to achieve long-life devices. In some embodiments, the amount of amino and / or carboxyl ligands with 3-4 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 4:1 to 10:1. In some embodiments, the amount of amino and / or carboxyl ligands with 5-7 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 1:1 to 5:1. When the chain length is longer (5-7), the electron mobility of the sample decreases after ligand exchange, similar to the effect of increased hydroxyl content; therefore, the amount of ligands with longer chains should not be excessive. Conversely, when the chain length is shorter (3-4), the migration rate of the sample increases after ligand exchange, similar to the effect of decreased hydroxyl content; therefore, the amount of ligands with longer chains can be increased.

[0113] In some embodiments, zinc salt solution, alkali solution, and amine ligands and / or carboxyl ligands with 3-7 carbon atoms are reacted at a temperature of 0-70°C for 30 minutes to 4 hours to prepare zinc oxide nanoparticles with amine ligands and / or carboxyl ligands with 3-7 carbon atoms on their surface. In some embodiments, the zinc salt solution and alkali solution are mixed as follows: zinc salt is dissolved at room temperature (5°C-40°C) to obtain a zinc salt solution; alkali is dissolved or diluted at room temperature to obtain an alkali solution; amine ligands and / or carboxyl ligands with 3-7 carbon atoms are dissolved at room temperature to obtain a ligand solution; the temperature of the zinc salt solution is adjusted to 0-70°C, and the alkali solution and ligand solution are added. In this case, the added alkali reacts with the zinc salt in the zinc salt solution to generate zinc oxide nanoparticles, and the added ligands exchange with the hydroxyl ligands on the surface of the zinc oxide nanoparticles, resulting in zinc oxide nanoparticles with amine ligands and / or carboxyl ligands with 3-7 carbon atoms on their surface, and good particle dispersibility is obtained. When the reaction temperature is below 0°C, the formation of zinc oxide nanoparticles is significantly slowed down, or even difficult to form, resulting only in hydroxide intermediates. Conversely, when the reaction temperature is above 70°C, the resulting zinc oxide nanoparticles exhibit severe aggregation and poor dispersibility, affecting the later film formation of the zinc oxide colloidal solution. In some embodiments, the reaction temperature between the zinc salt solution and the alkaline solution is room temperature to 50°C. Under these conditions, not only is the formation of zinc oxide nanoparticles favorable, but the resulting zinc oxide ions also exhibit better particle dispersibility, which is beneficial for the film formation of the zinc oxide colloidal solution.

[0114] In some embodiments, in the step of mixing the zinc salt solution with the alkaline solution, the zinc salt solution and the alkaline solution are mixed in a molar ratio of hydroxide ions to zinc ions of 1.5:1 to 2.5:1 to ensure the formation of zinc oxide nanoparticles and reduce the generation of reaction byproducts. When the molar ratio of hydroxide ions to zinc ions is less than 1.5:1, the zinc salt is significantly in excess, making it difficult for a large amount of zinc salt to form zinc oxide nanoparticles; while when the molar ratio of hydroxide ions to zinc ions is greater than 2.5:1, the alkaline solution is significantly in excess, and the excess hydroxide ions form a stable complex with the zinc hydroxide intermediate, making it difficult to condense and form zinc oxide nanoparticles. In some embodiments, in the step of mixing the zinc salt solution with the alkaline solution, the amount of zinc salt solution and alkaline solution added satisfies the following condition: the molar ratio of hydroxide ions provided by the alkaline solution to zinc ions provided by the zinc salt is 1.7:1 to 1.9:1.

[0115] In some embodiments, after mixing the zinc salt solution with the alkaline solution, the reaction is carried out at the reaction temperature for 30 minutes to 4 hours to ensure the formation of zinc oxide nanoparticles and control the particle size. When the reaction time is less than 30 minutes, the reaction time is too short, the formation of zinc oxide nanoparticles is insufficient, and the resulting nanoparticles have poor crystallinity; while when the reaction time exceeds 4 hours, the excessively long particle growth time results in excessively large nanoparticles with uneven particle size, affecting the later film-forming properties of the zinc oxide colloidal solution. In some embodiments, after adding the amine ligand with 3-7 carbon atoms and / or carboxyl ligand, the reaction is carried out for 10 minutes to 2 hours. In some embodiments, after mixing the zinc salt solution with the alkaline solution, the reaction is carried out at the reaction temperature for 1 to 2 hours.

[0116] In some embodiments, a zinc salt solution, an alkaline solution, and an amine ligand with 3-7 carbon atoms and / or a carboxyl ligand are mixed and stirred at a temperature of 0-70°C to promote the uniformity of the reaction and the uniformity of the obtained zinc oxide nanoparticles.

[0117] In some embodiments, after the reaction is complete, a precipitant is added to the resulting mixture, and the precipitate is collected. The precipitant is a solvent with an opposite polarity to the final product, zinc oxide nanoparticles, thereby reducing their solubility and precipitating them. In some embodiments, a weakly polar solvent is chosen as the precipitant, as this type of precipitant has an opposite polarity to the zinc oxide nanoparticles, which is beneficial for their precipitation. Exemplary precipitants include, but are not limited to, ethyl acetate, acetone, n-hexane, n-heptane, and other low-polarity long-chain alkanes.

[0118] In some embodiments, 2 to 6 times the volume of precipitant is added to the mixed solution after the reaction (i.e., the volume ratio of precipitant to mixed solution is 2:1 to 6:1), resulting in a white precipitate in the mixed solution. This ensures that the zinc oxide nanoparticles are fully precipitated without compromising their solubility due to excessive precipitant. In some embodiments, the volume ratio of precipitant to mixed solution is 3:1 to 5:1.

[0119] In this embodiment, the precipitated mixture is centrifuged to collect the precipitate. In some embodiments, the collected precipitate is washed with a reaction solvent to remove reactants that did not participate in the reaction. Washing the obtained zinc oxide nanoparticles with a reaction solvent can remove excess zinc salts, alkalis, and other raw materials used in the preparation of zinc oxide nanoparticles, thereby improving the purity of the zinc oxide nanoparticles. It should be noted that the reaction solvent is as described above. In some embodiments, the reaction solvent is selected from at least one of water, organic alcohols, organic ethers, and sulfones. These types of reaction solvents have high polarity and can effectively remove residual zinc salts, alkalis, and other raw material impurities, as well as intermediate impurities, from the zinc oxide nanoparticles. For example, the reaction solvent is selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO.

[0120] The precipitate after cleaning was dissolved to obtain a zinc oxide colloidal solution.

[0121] In the second implementation, an amine ligand with 3-7 carbon atoms and / or a carboxyl ligand are added during the intermediate stage of zinc oxide colloidal solution synthesis. That is, an amine ligand with 3-7 carbon atoms and / or a carboxyl ligand are added to the zinc oxide precursor solution that has already been added with alkali.

[0122] At this point, the steps for preparing zinc oxide colloidal solution by solution method include:

[0123] Zinc oxide nanoparticles with a surface-bound amino ligand and / or carboxyl ligand having 3-7 carbon atoms are prepared by mixing a zinc salt solution with an alkaline solution and reacting the solution during the reaction. The reaction time after adding the amino ligand and / or carboxyl ligand having 3-7 carbon atoms is greater than or equal to 10 minutes.

[0124] Zinc oxide nanoparticles were dissolved to obtain a zinc oxide colloidal solution.

[0125] In the above steps, the zinc salt solution is a salt solution formed by dissolving zinc salt in a solvent, and the alkali solution is a solution formed by an alkali that can react with the zinc salt to produce zinc hydroxide. The selection of the zinc salt and solvent in the zinc salt solution, the alkali and its formation method in the alkali solution, the selection of the solvent, and the addition ratio of zinc salt and alkali solution in the reaction system are as described in the first implementation method above.

[0126] In some embodiments, the amine ligands and / or carboxyl ligands having 3-7 carbon atoms include, but are not limited to, propionic acid, propylamine, butyric acid, butylamine, hexanoic acid, and hexylamine. In some embodiments, the amine ligands and / or carboxyl ligands having 3-7 carbon atoms are prepared into a ligand solution and then reacted with a zinc salt solution and an alkaline solution. The solvent in the ligand solution is selected from solvents with high polarity, mainly considering the solubility of the reactants and products. For example, the solvent in the ligand solution is selected from at least one of methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO. In some embodiments, the amine ligands and / or carboxyl ligands having 3-7 carbon atoms are used as the ligand solution, and the concentration of the ligand solution is 0.2-0.4 mmol / L. When the ligand concentration is too low, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is too small, making it difficult to achieve effective ligand exchange. When the ligand concentration is too high, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is too large, and a large amount of ligands remaining in the solution will remain in the first electron transport layer, affecting the film formation quality and properties of the electron transport layer.

[0127] In this embodiment, the reaction temperature and time for mixing the zinc salt solution with the alkaline solution are as described in the first implementation method above.

[0128] In the embodiments of this application, amine ligands and / or carboxyl ligands with 3-7 carbon atoms are added during the reaction process to prepare zinc oxide nanoparticles with amine ligands and / or carboxyl ligands with 3-7 carbon atoms bound to their surface.

[0129] In some embodiments, the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms added satisfies the following condition: the molar ratio of the amine ligands and / or carboxyl ligands with 3-7 carbon atoms to the zinc salt in the zinc salt solution is 1:1 to 10:1. In this case, the added amine ligands and / or carboxyl ligands with 3-7 carbon atoms bind to the surface of the generated zinc oxide nanoparticles, reducing the number of hydroxyl ligands on the surface of the zinc oxide nanoparticles, thereby improving the lifespan of the device. However, if the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms is too large, too many ligands will be attached to the zinc oxide surface, reducing the electron mobility of zinc oxide and hindering the achievement of long-life devices; while if the amount of ligands is too small, too few ligands will be attached to the zinc oxide surface, making it difficult to reduce the amount of surface hydroxyl ligands, and also making it difficult to achieve long-life devices. In some embodiments, the amount of amino and / or carboxyl ligands with 3-4 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 4:1 to 10:1. In some embodiments, the amount of amino and / or carboxyl ligands with 5-7 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 1:1 to 5:1. When the chain length is longer (5-7), the electron mobility of the sample decreases after ligand exchange, similar to the effect of increased hydroxyl content; therefore, the amount of ligands with longer chain lengths should not be excessive. Conversely, when the chain length is shorter, the migration rate of the sample increases after ligand exchange, similar to the effect of decreased hydroxyl content; therefore, the amount of ligands with longer chain lengths can be increased.

[0130] It should be noted that after adding amine ligands with 3-7 carbon atoms and / or carboxyl ligands, the reaction time should be greater than or equal to 10 minutes to ensure sufficient exchange between the ligands and the hydroxyl groups on the surface of the generated zinc oxide nanoparticles (3-4). In some embodiments, after adding amine ligands with 3-7 carbon atoms and / or carboxyl ligands during the reaction, the mixture is stirred for 10 minutes to 2 hours to ensure the exchange reaction proceeds fully. In some embodiments, the stirring time is 30 minutes to 1 hour.

[0131] In some embodiments, after the reaction is complete, a precipitant is added to the resulting mixed solution, and the precipitate is collected. The selection and amount of the precipitant are as described in the first implementation above.

[0132] In this embodiment, the precipitated mixture is centrifuged to collect the precipitate. In some embodiments, the collected precipitate is washed with a reaction solvent to remove reactants that did not participate in the reaction. Washing the obtained zinc oxide nanoparticles with a reaction solvent can remove excess zinc salts, alkalis, and other raw materials used in the preparation of zinc oxide nanoparticles, thereby improving the purity of the zinc oxide nanoparticles. It should be noted that the reaction solvent is as described above. In some embodiments, the reaction solvent is selected from at least one of water, organic alcohols, organic ethers, and sulfones. These types of reaction solvents have high polarity and can effectively remove residual zinc salts, alkalis, and other raw material impurities, as well as intermediate impurities, from the zinc oxide nanoparticles. For example, the reaction solvent is selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO.

[0133] The precipitate after cleaning was dissolved to obtain a zinc oxide colloidal solution.

[0134] In the third implementation, an amino ligand with 3-7 carbon atoms and / or a carboxyl ligand are added after the zinc oxide colloidal solution is prepared.

[0135] At this point, the steps for preparing zinc oxide colloidal solution by solution method include:

[0136] After zinc oxide nanoparticles are prepared by mixing zinc salt solution with alkaline solution, amine ligands and / or carboxyl ligands with 3-7 carbon atoms are added and the reaction is continued to prepare zinc oxide nanoparticles with amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface.

[0137] Zinc oxide nanoparticles were dissolved to obtain a zinc oxide colloidal solution.

[0138] In the above steps, the zinc salt solution is a salt solution formed by dissolving zinc salt in a solvent, and the alkali solution is a solution formed by an alkali that can react with the zinc salt to produce zinc hydroxide. The selection of the zinc salt and solvent in the zinc salt solution, the alkali and its formation method in the alkali solution, the selection of the solvent, and the addition ratio of zinc salt and alkali solution in the reaction system are as described in the first implementation method above.

[0139] In some embodiments, the amino ligand and / or carboxyl ligand having 3-7 carbon atoms, the solvent selection in the ligand solution, and the concentration of the ligand solution are as described in the first implementation above.

[0140] In this embodiment, the reaction temperature and time for mixing the zinc salt solution with the alkaline solution are as described in the first implementation method above.

[0141] In this embodiment, after zinc oxide nanoparticles are prepared by reaction, an amine ligand and / or a carboxyl ligand with 3-7 carbon atoms are added to prepare zinc oxide nanoparticles with an amine ligand and / or a carboxyl ligand with 3-7 carbon atoms on the surface.

[0142] In some embodiments, the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms added satisfies the following condition: the molar ratio of the amine ligands and / or carboxyl ligands with 3-7 carbon atoms to the zinc salt in the zinc salt solution is 1:1 to 10:1. In this case, the added amine ligands and / or carboxyl ligands with 3-7 carbon atoms bind to the surface of the generated zinc oxide nanoparticles, reducing the number of hydroxyl ligands on the surface of the zinc oxide nanoparticles, thereby improving the lifespan of the device. However, if the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms is too large, too many ligands will be attached to the zinc oxide surface, reducing the electron mobility of zinc oxide and hindering the achievement of long-life devices; while if the amount of ligands is too small, too few ligands will be attached to the zinc oxide surface, making it difficult to reduce the amount of surface hydroxyl ligands, and also making it difficult to achieve long-life devices. In some embodiments, the amount of amino and / or carboxyl ligands with 3-4 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 4:1 to 10:1. In some embodiments, the amount of amino and / or carboxyl ligands with 5-7 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 1:1 to 5:1. When the chain length is longer (5-7), the electron mobility of the sample decreases after ligand exchange, similar to the effect of increased hydroxyl content; therefore, the amount of ligands with longer chain lengths should not be excessive. Conversely, when the chain length is shorter, the migration rate of the sample increases after ligand exchange, similar to the effect of decreased hydroxyl content; therefore, the amount of ligands with longer chain lengths can be increased.

[0143] It should be noted that after adding an amino ligand with 3-7 carbon atoms and / or a carboxyl ligand, the reaction should continue for at least 10 minutes to ensure sufficient exchange between the ligand and the hydroxyl groups on the surface of the generated zinc oxide nanoparticles. In some embodiments, after adding the amino ligand with 3-7 carbon atoms and / or a carboxyl ligand during the reaction, the mixture is stirred for 10 minutes to 2 hours to ensure the exchange reaction proceeds fully. In some embodiments, the stirring time is 30 minutes to 1 hour.

[0144] In some embodiments, after the reaction is complete, a precipitant is added to the mixed solution after the reaction, and the precipitate is collected. The selection and amount of the precipitant are as described in the first implementation above.

[0145] In this embodiment, the precipitated mixture is centrifuged to collect the precipitate. In some embodiments, the collected precipitate is washed with a reaction solvent to remove reactants that did not participate in the reaction. Washing the obtained zinc oxide nanoparticles with a reaction solvent can remove excess zinc salts, alkalis, and other raw materials used in the preparation of zinc oxide nanoparticles, thereby improving the purity of the zinc oxide nanoparticles. It should be noted that the reaction solvent is as described above. In some embodiments, the reaction solvent is selected from at least one of water, organic alcohols, organic ethers, and sulfones. These types of reaction solvents have high polarity and can effectively remove residual zinc salts, alkalis, and other raw material impurities, as well as intermediate impurities, from the zinc oxide nanoparticles. For example, the reaction solvent is selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO.

[0146] The precipitate after cleaning was dissolved to obtain a zinc oxide colloidal solution.

[0147] In the fourth implementation, after preparing zinc oxide nanoparticles and cleaning them, an amino ligand with 3-7 carbon atoms and / or a carboxyl ligand are added.

[0148] At this point, the steps for preparing zinc oxide colloidal solution by solution method include:

[0149] Zinc salt solution was mixed with alkaline solution and reacted. The product was collected, washed, and then zinc oxide nanoparticles were obtained.

[0150] After dissolving zinc oxide nanoparticles, amine ligands and / or carboxyl ligands with 3-7 carbon atoms are added to react and bind amine ligands and / or carboxyl ligands with 3-7 carbon atoms to the surface of zinc oxide, thus obtaining a zinc oxide colloidal solution.

[0151] In the above steps, the zinc salt solution is a salt solution formed by dissolving zinc salt in a solvent, and the alkali solution is a solution formed by an alkali that can react with the zinc salt to produce zinc hydroxide. The selection of the zinc salt and solvent in the zinc salt solution, the alkali and its formation method in the alkali solution, the selection of the solvent, and the addition ratio of zinc salt and alkali solution in the reaction system are as described in the first implementation method above.

[0152] In the embodiments, the reaction temperature and time of the zinc salt solution reaction are as described in the first implementation method above.

[0153] In some embodiments, after the reaction is complete, a precipitant is added to the mixed solution after the reaction, and the precipitate is collected. The selection and amount of the precipitant are as described in the first implementation above.

[0154] In this embodiment, the precipitated mixture is centrifuged to collect the product. In some embodiments, the collected product is washed with a reaction solvent to remove reactants that did not participate in the reaction. Washing the obtained zinc oxide nanoparticles with a reaction solvent can remove excess zinc salts, alkalis, and other raw materials used in the preparation of zinc oxide nanoparticles, thereby improving the purity of the zinc oxide nanoparticles. It should be noted that the reaction solvent is as described above. In some embodiments, the reaction solvent is selected from at least one of water, organic alcohols, organic ethers, and sulfones. These types of reaction solvents have high polarity and can effectively remove residual zinc salts, alkalis, and other raw material impurities, as well as intermediate impurities, from the zinc oxide nanoparticles. For example, the reaction solvent is selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO.

[0155] In this embodiment, zinc oxide nanoparticles are dissolved, and then an amine ligand with 3-7 carbon atoms and / or a carboxyl ligand are added to react and bind the amine ligand with 3-7 carbon atoms to the surface of zinc oxide, thus obtaining a zinc oxide colloidal solution.

[0156] In some embodiments, the amino ligands and / or carboxyl ligands having 3-7 carbon atoms include, but are not limited to, propionic acid, propylamine, butyric acid, butylamine, hexanoic acid, and hexylamine. In some embodiments, the amino ligands and / or carboxyl ligands having 3-7 carbon atoms are prepared into a ligand solution and then reacted with a zinc salt solution and an alkaline solution. The solvent in the ligand solution is selected from solvents with high polarity, mainly considering the solubility of the reactants and products. For example, the solvent in the ligand solution is selected from at least one of methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO. In some embodiments, the amino ligands and / or carboxyl ligands having 3-7 carbon atoms are in the ligand solution, and the concentration of the ligand solution is 0.05-0.1 mmol / L.

[0157] In some embodiments, the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms added satisfies the following condition: the molar ratio of the amine ligands and / or carboxyl ligands with 3-7 carbon atoms to the zinc salt in the zinc salt solution is 1:4 to 4:1. In this case, the added amine ligands and / or carboxyl ligands with 3-7 carbon atoms bind to the surface of the generated zinc oxide nanoparticles, reducing the number of hydroxyl ligands on the surface of the zinc oxide nanoparticles, thereby improving the lifespan of the device. However, if the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms is too large, too many ligands will be attached to the zinc oxide surface, reducing the electron mobility of zinc oxide and hindering the achievement of long-life devices; while if the amount of ligands is too small, too few ligands will be attached to the zinc oxide surface, making it difficult to reduce the amount of surface hydroxyl ligands, and also making it difficult to achieve long-life devices. In some embodiments, the amount of amino and / or carboxyl ligands with 3-4 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 4:1 to 10:1. In some embodiments, the amount of amino and / or carboxyl ligands with 5-7 carbon atoms and 3-7 carbon atoms added satisfies the following condition: the molar ratio of amino and / or carboxyl ligands to zinc salt in the zinc salt solution is 1:1 to 5:1. When the chain length is longer (5-7), the electron mobility of the sample decreases after ligand exchange, similar to the effect of increased hydroxyl content; therefore, the amount of ligands with longer chain lengths should not be excessive. Conversely, when the chain length is shorter, the migration rate of the sample increases after ligand exchange, similar to the effect of decreased hydroxyl content; therefore, the amount of ligands with longer chain lengths can be increased.

[0158] It should be noted that after adding an amino ligand with 3-7 carbon atoms and / or a carboxyl ligand, the reaction should continue for at least 10 minutes to ensure sufficient exchange between the ligand and the hydroxyl groups on the surface of the generated zinc oxide nanoparticles. In some embodiments, after adding the amino ligand with 3-7 carbon atoms and / or a carboxyl ligand during the reaction, the mixture is stirred for 10 minutes to 2 hours to ensure the exchange reaction proceeds fully. In some embodiments, the stirring time is 30 minutes to 1 hour.

[0159] In one possible implementation, the first electron transport layer is a metal-doped zinc oxide thin film. Correspondingly, the zinc oxide in the first electron transport layer is metal-doped zinc oxide, and the zinc salt solution also contains doped metal ions. In this embodiment, the selection of the doped metal ions and their doping content are as described above.

[0160] In some embodiments, the doping metal ion is selected from Mg. 2+ Mn 2+ At least one of the following. In some embodiments, the doping metal ion is selected from Al. 3+ Y 3+La 3+ Li + Gd 3+ Zr 4+ Ce 4+ At least one of them.

[0161] In some embodiments, the zinc salt solution contains zinc ions and doped metal ions, and in the step of mixing the zinc salt solution with the alkali solution, the added amounts of zinc salt solution and alkali solution satisfy the following: the ratio of the product of the molar amount and valence of the metal ion to the molar amount of hydroxide ions is 0.75:1 to 1.25:1. In this case, mixing the zinc salt solution with the alkali solution ensures the formation of metal-doped zinc oxide nanoparticles and reduces the generation of reaction byproducts. When the molar ratio of hydroxide ions to metal ions is less than 0.75:1, the metal ion content is excessive, making it difficult for the metal salt to form metal-doped zinc oxide nanoparticles; while when the molar ratio of hydroxide ions to zinc ions is greater than 1.25:1, the alkali solution is significantly excessive, and the excess hydroxide ions form a stable complex with the zinc hydroxide intermediate, making it difficult to condense and form zinc oxide nanoparticles. In some embodiments, in the step of mixing the zinc salt solution with the alkaline solution, the amount of zinc salt solution and alkaline solution added satisfies the ratio of the product of the molar amount of the metal ion and its valence to the molar amount of hydroxide ion being 0.85:1 to 0.95:1.

[0162] In step S12 above, the zinc oxide colloidal solution can be formed on the pre-fabricated device substrate according to the type of quantum dot light-emitting diode device being prepared. The solvent is then removed to obtain a zinc oxide film with amine ligands and / or carboxyl ligands with 3-7 carbon atoms bonded to the surface of the zinc oxide.

[0163] In some embodiments, the zinc oxide colloidal solution is formed on the prefabricated device substrate using one of the following methods, including but not limited to spin coating, blade coating, printing, spraying, roller coating, and electrodeposition. After forming the zinc oxide colloidal solution on the prefabricated device substrate, the solvent is removed by annealing to obtain a zinc oxide film with amine ligands and / or carboxyl ligands having 3-7 carbon atoms bonded to its surface.

[0164] In one possible implementation, the quantum dot light-emitting diode is a positive quantum dot light-emitting diode, and the prefabrication substrate includes an anode substrate and a quantum dot light-emitting layer bonded to the anode substrate. In some embodiments, the prefabrication substrate further includes a hole functional layer disposed between the anode substrate and the quantum dot light-emitting layer. The hole functional layer includes at least one of a hole transport layer, a hole injection layer, and an electron blocking layer.

[0165] In one possible implementation, the quantum dot light-emitting diode is an inverted quantum dot light-emitting diode, and the prefabrication substrate is a cathode substrate. In some embodiments, the prefabrication substrate further includes an electron injection layer bonded to the cathode surface of the cathode substrate.

[0166] In some embodiments, the first electron transport layer may serve as the electron transport layer alone.

[0167] In some embodiments, the electron transport layer comprises two zinc oxide films or n film stack units composed of two zinc oxide films, wherein the two zinc oxide films are respectively named the first electron transport layer and the second electron transport layer, and n is greater than or equal to 2. In some embodiments, n is an integer greater than or equal to 2 and less than or equal to 9. At least the first electron transport layer is a zinc oxide film prepared by the above method with amine ligands and / or carboxyl ligands having 3-7 carbon atoms bonded to its surface. The case of the second electron transport layer can be referred to the case of the second electron transport layer in the quantum dot light-emitting diode device described above.

[0168] In some embodiments, the second electron transport layer is a zinc oxide film with a surface hydroxyl content greater than or equal to 0.6, or the second electron transport layer is a metal-doped zinc oxide film. The first electron transport layer can be disposed on the side adjacent to the quantum dot light-emitting layer or on the side adjacent to the cathode. Preferably, disposing the first electron transport layer on the side adjacent to the quantum dot light-emitting layer or disposing the metal-doped zinc oxide film on the side adjacent to the quantum dot light-emitting layer results in a smoother zinc oxide film.

[0169] In some embodiments, the electron transport layer comprises three zinc oxide films, which are respectively named the first electron transport layer, the second electron transport layer, and the third electron transport layer. At least the first electron transport layer is a zinc oxide film prepared by the above method with amine ligands and / or carboxyl ligands having 3-7 carbon atoms bonded to its surface. The second and third electron transport layers can be referenced to the case described above regarding the inclusion of a third electron transport layer in quantum dot light-emitting diode devices.

[0170] In the above embodiments, zinc oxide films with a surface hydroxyl content greater than or equal to 0.6 can be formed by zinc oxide colloidal solutions with a surface hydroxyl content greater than or equal to 0.6.

[0171] In the above embodiments, zinc oxide films with a surface hydroxyl content of less than or equal to 0.4 can be formed by zinc oxide colloidal solutions with a surface hydroxyl content of less than or equal to 0.4.

[0172] In the above embodiments, the metal-doped zinc oxide thin film can be prepared according to the following method:

[0173] Under conditions of 0–70°C, a zinc salt solution containing doped metal ions is mixed with an alkaline solution and reacted for 30 minutes to 4 hours. A precipitant is added to the mixed solution after the reaction, and the precipitate is collected. After washing the precipitate with a reaction solvent, the resulting white precipitate is dissolved to obtain a doped zinc oxide colloidal solution. The doped zinc oxide colloidal solution is then formed on a substrate on which a metal-doped zinc oxide thin film is to be prepared, thus obtaining a metal-doped zinc oxide thin film. In this embodiment, the type of zinc salt and solvent, the content of zinc salt solution, the type and content of doped ions, the type and amount of alkaline solution added, the reaction temperature and reaction time, and the selection and amount of precipitant added are all performed according to step S11 of the embodiments of this application. In this method, the zinc salt solution containing doped metal ions can be obtained by dissolving zinc salt and a selected metal salt in a solvent at room temperature in a certain proportion. In the step of mixing the zinc salt solution containing doped metal ions with an alkaline solution, the amount of alkali added satisfies the following condition: the ratio of the product of the molar amount of the metal ion and its valence to the molar amount of the hydroxide ion is 0.75:1 to 1.25:1.

[0174] In a second embodiment, this application provides a method for fabricating a quantum dot light-emitting diode (LED). The quantum dot LED includes an anode and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The electron transport layer includes a first electron transport layer containing zinc oxide, and at least one side surface of the first electron transport layer contains an amino ligand and / or a carboxyl ligand with 3-7 carbon atoms.

[0175] Among them, such as Figure 7 As shown, the method for fabricating the first electron transport layer includes:

[0176] S21. Prepare a zinc oxide pre-film on the pre-fabricated device substrate on which the first electron transport layer is to be prepared;

[0177] S22. After depositing a solution of amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface of a zinc oxide pre-film, the film is dried to obtain a zinc oxide film.

[0178] The method for fabricating quantum dot light-emitting diodes provided in this application involves depositing a solution of amine and / or carboxyl ligands with 3-7 carbon atoms on the surface of a zinc oxide pre-film. This promotes ligand exchange between the amine and / or carboxyl ligands and the hydroxyl ligands on the surface of the zinc oxide colloid, thereby coordinating the amine and / or carboxyl ligands with 3-7 carbon atoms onto the surface of the zinc oxide colloid. Because the chain length of the coordinated amine and / or carboxyl ligands is relatively short, it does not significantly increase the distance between zinc oxide nanoparticles in the solution or after film formation. Simultaneously, it reduces the amount of hydroxyl groups on the surface of the zinc oxide nanoparticles, thereby increasing the electron mobility of the zinc oxide electron transport layer after film formation and effectively improving the lifetime of the quantum dot light-emitting diode device.

[0179] In the embodiments of this application, the composition of the quantum dot light-emitting diode, especially the electron transport layer, is as described in the first aspect above, and will not be repeated here for the sake of brevity.

[0180] In step S21 above, the zinc oxide pre-film can be prepared in a variety of ways. For example, the zinc oxide pre-film can be prepared by solution method or sol-gel method.

[0181] In some embodiments, the zinc oxide pre-film is prepared by a solution method, comprising: mixing and reacting a zinc salt solution with an alkaline solution to prepare zinc oxide nanoparticles; dissolving the zinc oxide nanoparticles to obtain a zinc oxide colloidal solution; forming the zinc oxide colloidal solution on a pre-fabricated device substrate on which the first electron transport layer is to be prepared; removing the solvent to obtain the zinc oxide pre-film.

[0182] Zinc oxide colloidal solutions can be prepared by solution methods, such as alcoholysis or hydrolysis. The basic process for preparing zinc oxide by solution methods is as follows: a zinc salt solution is mixed with an alkaline solution, which reacts to generate a hydroxide intermediate, such as zinc hydroxide; the hydroxide intermediate undergoes a condensation reaction to gradually generate zinc oxide nanoparticles.

[0183] In this embodiment, the selection criteria and types of the zinc salt solution, the zinc salt in the zinc salt solution, and the solvent, as well as the formation method of the zinc salt solution, are as described in the first embodiment above.

[0184] In this embodiment, the selection criteria and types of the alkaline solution, the alkali in the alkaline solution, and the solvent, as well as the formation method of the alkaline solution, are as described in the first embodiment above.

[0185] In some embodiments, zinc salt solution and alkaline solution are mixed and treated at a temperature of 0–70°C for 30 min–4 h to prepare zinc oxide nanoparticles. In some embodiments, the mixing of zinc salt solution and alkaline solution is performed as follows: zinc salt is dissolved at room temperature (5°C–40°C) to obtain a zinc salt solution; an alkaline solution is obtained by dissolving or diluting an alkali at room temperature; the temperature of the zinc salt solution is adjusted to 0–70°C, and then the alkaline solution is added. In this case, the added alkali reacts with the zinc salt in the zinc salt solution to generate zinc oxide nanoparticles, achieving good particle dispersibility. When the reaction temperature is below 0°C, the generation of zinc oxide nanoparticles is significantly slowed down, and the reaction requires special equipment, increasing the difficulty of the reaction. Under some conditions, it is even difficult to generate zinc oxide nanoparticles, and only hydroxide intermediates are obtained. When the reaction temperature is above 70°C, the reactivity is too high, and the generated zinc oxide nanoparticles agglomerate severely, making it difficult to obtain a well-dispersed colloidal solution, affecting the later film formation of the zinc oxide colloidal solution. In some embodiments, the reaction temperature of the zinc salt solution and the alkaline solution is room temperature to 50°C. Under these conditions, not only is the formation of zinc oxide nanoparticles favorable, but the resulting zinc oxide ions also exhibit good particle dispersion, which is beneficial for the film formation of the zinc oxide colloidal solution. In some embodiments, mixing the zinc salt solution and the alkaline solution at a temperature of 0 to 30°C can easily generate a qualified zinc oxide colloidal solution. In some embodiments, a zinc oxide colloidal solution can also be generated at a temperature of 30°C to 70°C, but the quality of the resulting zinc oxide colloidal solution is not as good as that generated at 0 to 30°C, and the reaction time is also reduced.

[0186] In some embodiments, in the step of mixing the zinc salt solution with the alkaline solution, the zinc salt solution and the alkaline solution are mixed in a molar ratio of hydroxide ions to zinc ions of 1.5:1 to 2.5:1 to ensure the formation of zinc oxide nanoparticles and reduce the generation of reaction byproducts. When the molar ratio of hydroxide ions to zinc ions is less than 1.5:1, the zinc salt is significantly in excess, making it difficult for a large amount of zinc salt to form zinc oxide nanoparticles; while when the molar ratio of hydroxide ions to zinc ions is greater than 2.5:1, the alkaline solution is significantly in excess, and the excess hydroxide ions form a stable complex with the zinc hydroxide intermediate, making it difficult to condense and form zinc oxide nanoparticles. In some embodiments, in the step of mixing the zinc salt solution with the alkaline solution, the amount of zinc salt solution and alkaline solution added satisfies the following condition: the molar ratio of hydroxide ions provided by the alkaline solution to zinc ions provided by the zinc salt is 1.7:1 to 1.9:1.

[0187] In this embodiment, the zinc salt solution and alkaline solution are mixed and reacted at a reaction temperature of 0–70°C for 30 min–4 h to ensure the formation of zinc oxide nanoparticles and control the particle size. When the reaction time is less than 30 min, the reaction results in zinc oxide clusters, which have incomplete crystallization and poor crystal structure. If used as an electron transport layer material, this would lead to poor conductivity of the electron transport layer. When the reaction time exceeds 4 h, the excessively long particle growth time results in excessively large and unevenly sized nanoparticles. The surface roughness of the zinc oxide colloidal solution film is high, affecting electron transport performance. In some embodiments, the zinc salt solution and alkaline solution are mixed and reacted at the reaction temperature for 1–2 h.

[0188] In some embodiments, zinc salt solution and alkaline solution are mixed at a temperature of 0 to 70°C and reacted for 30 min to 4 h under stirring conditions to promote the uniformity of the reaction and the particle uniformity of the obtained zinc oxide nanoparticles, thereby obtaining zinc oxide nanoparticles with uniform size.

[0189] In this embodiment, the zinc oxide nanoparticles are dissolved to obtain a zinc oxide colloidal solution.

[0190] In some embodiments, the method for obtaining zinc oxide nanoparticles further includes: after the reaction is complete, adding a precipitant to the mixed solution after the reaction and collecting the precipitate. The precipitant is selected from solvents with opposite polarity to the final product, zinc oxide nanoparticles, thereby reducing the solubility of the zinc oxide nanoparticles and precipitating them. In some embodiments, the precipitant is selected from solvents with low polarity, which is opposite to the polarity of the zinc oxide nanoparticles and facilitates their precipitation. Exemplary precipitants include, but are not limited to, ethyl acetate, acetone, n-hexane, n-heptane, and other low-polarity long-chain alkanes.

[0191] In some embodiments, 2 to 6 times the volume of precipitant is added to the mixed solution after the reaction (i.e., the volume ratio of precipitant to mixed solution is 2:1 to 6:1), resulting in a white precipitate in the mixed solution. This ensures that the zinc oxide nanoparticles are fully precipitated without compromising their solubility due to excessive precipitant. In some embodiments, the volume ratio of precipitant to mixed solution is 3:1 to 5:1.

[0192] In this embodiment, the precipitated mixture is centrifuged to collect the precipitate. The collected precipitate is then washed with a reaction solvent to remove unreacted reactants. Washing the obtained zinc oxide nanoparticles with the reaction solvent removes excess zinc salts, alkalis, and other raw materials used in the preparation of the zinc oxide nanoparticles, thereby improving their purity. It should be noted that the reaction solvent is as described above. In some embodiments, the reaction solvent is selected from at least one of water, organic alcohols, organic ethers, and sulfones. For example, the reaction solvent is selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO.

[0193] After cleaning, a white precipitate was obtained. The white precipitate was dissolved to obtain a zinc oxide colloidal solution.

[0194] In one possible implementation, the first electron transport layer is a metal-doped zinc oxide thin film. Correspondingly, the zinc oxide in the first electron transport layer is metal-doped zinc oxide, and the zinc salt solution also contains doped metal ions. In this embodiment, the selection of the doped metal ions and the doping content are similar to the selection of the doped metal in the metal-doped zinc oxide thin film described above.

[0195] In this embodiment, the zinc oxide colloidal solution can be formed on the prefabricated device substrate on which the first electron transport layer is to be prepared, depending on the type of quantum dot light-emitting diode device being prepared. The solvent is then removed to obtain a zinc oxide prefabricated thin film.

[0196] In some embodiments, the zinc oxide colloidal solution is formed on the prefabricated device substrate using one of the following methods, including but not limited to spin coating, blade coating, printing, spraying, roller coating, and electrodeposition. After forming the zinc oxide colloidal solution on the prefabricated device substrate, the solvent is removed by annealing to obtain a zinc oxide pre-film.

[0197] In some embodiments, zinc oxide pre-films are prepared by a sol-gel method (high-temperature calcination method). Specifically, zinc oxide precursors are directly spin-coated onto a substrate on which the zinc oxide pre-film is to be prepared, and then subjected to high-temperature heat treatment to convert it into zinc oxide.

[0198] In step S22 above, by depositing an amino ligand and / or carboxyl ligand solution with 3-7 carbon atoms on the zinc oxide pre-film, ligand exchange is promoted between the amino ligand and / or carboxyl ligand and the hydroxyl ligand on the surface of the zinc oxide colloid, thereby coordinating the amino ligand and / or carboxyl ligand with 3-7 carbon atoms on the surface of the zinc oxide colloid.

[0199] In this embodiment, the coordination solution of amine ligands and / or carboxyl ligands with 3-7 carbon atoms refers to a ligand solution obtained by coordinating and dissolving amine ligands and / or carboxyl ligands with 3-7 carbon atoms in a solvent. In some embodiments, amine ligands and / or carboxyl ligands with 3-7 carbon atoms include, but are not limited to, propionic acid, propylamine, butyric acid, butylamine, hexanoic acid, and hexylamine. In some embodiments, the solvent used to dissolve amine ligands and / or carboxyl ligands with 3-7 carbon atoms includes, but is not limited to, a highly polar solvent such as water or alcohols. For example, the solvent used to dissolve amine ligands and / or carboxyl ligands with 3-7 carbon atoms is selected from at least one of water, methanol, ethanol, propanol, butanol, ethylene glycol, ethylene glycol monomethyl ether, and DMSO.

[0200] In this embodiment, the concentration and amount of the amino ligands and / or carboxyl ligands with 3-7 carbon atoms in the solution need to be controlled. This is because: when the ligand concentration is too low, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is too small, making it difficult to achieve effective ligand exchange; while when the ligand concentration is too high, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is too large, and a large amount of ligands remaining in the solution will directly remain in the final first electron transport layer, affecting the film quality and properties of the electron transport layer. In some embodiments, the concentration of the amino ligands and / or carboxyl ligands with 3-7 carbon atoms in the ligand solution is 0.05-0.5 mmol / L. When the ligand concentration is too low, the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms added is too small, making it difficult to achieve effective ligand exchange. When the ligand concentration is too high, the amount of amine ligands and / or carboxyl ligands with 3-7 carbon atoms added is too large, and a large amount of ligands remaining in the solution will directly remain in the final first electron transport layer, affecting the film quality and properties of the electron transport layer.

[0201] In some embodiments, the concentration of the ligand solution containing 3-7 carbon atoms (amino and / or carboxyl ligands) is 0.05-0.5 mmol / L. In the step following the deposition of the 3-7 carbon atoms ligand solution on the surface of the zinc oxide pre-film, the amount of 3-7 carbon atoms ligands added is: 50 μL-1000 μL of 3-7 carbon atoms ligand solution per 5 mg of zinc oxide pre-film. When the ligand chain length is long (5-7), the electron mobility of the sample decreases after ligand exchange, similar to the effect of increased hydroxyl content; therefore, the amount of long-chain ligands added should not be excessive. Conversely, when the ligand chain length is short (3-4), the migration rate of the sample increases after ligand exchange, similar to the effect of decreased hydroxyl content; therefore, the amount of long-chain ligands added can be greater. In some embodiments, when the number of carbon atoms in the amino ligands and / or carboxyl ligands with 3-7 carbon atoms is 3-4, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is: 100 μL-500 μL of amino ligands and / or carboxyl ligands with 3-7 carbon atoms deposited per 5 mg of zinc oxide pre-film; when the number of carbon atoms in the amino ligands and / or carboxyl ligands with 3-7 carbon atoms is 5-7, the amount of amino ligands and / or carboxyl ligands with 3-7 carbon atoms added is: 50 μL-400 μL of amino ligands and / or carboxyl ligands with 3-7 carbon atoms deposited per 5 mg of zinc oxide pre-film.

[0202] In the embodiments of this application, the method of depositing an amine ligand and / or carboxyl ligand solution with 3-7 carbon atoms on the surface of the zinc oxide pre-film can be a solution processing method, including but not limited to one of spin coating, blade coating, printing, spraying, roller coating, electrodeposition, etc.

[0203] After depositing a solution of amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface of a zinc oxide pre-film, a drying process is performed. This drying process allows the ligands in the amine ligands and / or carboxyl ligands with 3-7 carbon atoms to fully exchange with the hydroxyl groups on the zinc oxide surface. In some embodiments, the drying temperature is 10°C to 100°C, and the drying time is 10 minutes to 2 hours. In this case, the electroligands in the amine ligands and / or carboxyl ligands with 3-7 carbon atoms fully react with the hydroxyl groups on the zinc oxide surface, thereby reducing the amount of hydroxyl groups on the zinc oxide surface. If the drying temperature is too high or the drying time is too long, the amine ligands and / or carboxyl ligands with 3-7 carbon atoms will dry rapidly, and the zinc oxide pre-film will quickly become a solid film. This makes it difficult for the ligands in the amine ligands and / or carboxyl ligands with 3-7 carbon atoms to fully react with the hydroxyl groups on the zinc oxide surface, thus failing to sufficiently reduce the amount of hydroxyl groups on the zinc oxide surface. Conversely, if the drying temperature is too low or the drying time is too short, the zinc oxide pre-film will be difficult to dry fully, affecting the preparation of the next layer, especially the electrode deposition quality. In some embodiments, the drying temperature is 10°C to 50°C, and the drying time is 30 minutes to 2 hours.

[0204] In one possible implementation, the quantum dot light-emitting diode is a positive quantum dot light-emitting diode, and the prefabrication substrate includes an anode substrate and a quantum dot light-emitting layer bonded to the anode substrate. In some embodiments, the prefabrication substrate further includes a hole functional layer disposed between the anode substrate and the quantum dot light-emitting layer. The hole functional layer includes at least one of a hole transport layer, a hole injection layer, and an electron blocking layer.

[0205] In one possible implementation, the quantum dot light-emitting diode is an inverted quantum dot light-emitting diode, and the prefabrication substrate is a cathode substrate. In some embodiments, the prefabrication substrate further includes an electron injection layer bonded to the cathode surface of the cathode substrate.

[0206] In some embodiments, the first electron transport layer may serve as the electron transport layer alone.

[0207] In some embodiments, the electron transport layer comprises two zinc oxide films or n film stack units composed of two zinc oxide films, wherein the two zinc oxide films are respectively named the first electron transport layer and the second electron transport layer, and n is greater than or equal to 2. In some embodiments, n is an integer greater than or equal to 2 and less than or equal to 9. At least the first electron transport layer is a zinc oxide film prepared by the above method with amine ligands and / or carboxyl ligands having 3-7 carbon atoms bonded to its surface. The case of the second electron transport layer can be referred to the case of the second electron transport layer in the quantum dot light-emitting diode device described above.

[0208] In some embodiments, the second electron transport layer is a zinc oxide film with a surface hydroxyl content greater than or equal to 0.6, or the second electron transport layer is a metal-doped zinc oxide film. The first electron transport layer can be disposed on the side adjacent to the quantum dot light-emitting layer or on the side adjacent to the cathode. Preferably, disposing the first electron transport layer on the side adjacent to the quantum dot light-emitting layer or disposing the metal-doped zinc oxide film on the side adjacent to the quantum dot light-emitting layer results in a smoother zinc oxide film.

[0209] In some embodiments, the electron transport layer comprises three zinc oxide films, which are respectively named the first electron transport layer, the second electron transport layer, and the third electron transport layer. At least the first electron transport layer is a zinc oxide film prepared by the above method with amine ligands and / or carboxyl ligands having 3-7 carbon atoms bonded to its surface. The second and third electron transport layers can be referenced to the case described above regarding the inclusion of a third electron transport layer in quantum dot light-emitting diode devices.

[0210] In the above embodiments, zinc oxide films with a surface hydroxyl content greater than or equal to 0.6 can be formed by zinc oxide colloidal solutions with a surface hydroxyl content greater than or equal to 0.6.

[0211] In the above embodiments, zinc oxide films with a surface hydroxyl content of less than or equal to 0.4 can be formed by zinc oxide colloidal solutions with a surface hydroxyl content of less than or equal to 0.4.

[0212] In the above embodiments, the metal-doped zinc oxide thin film, as described above, will not be repeated here for the sake of brevity.

[0213] It should be understood that in the two embodiments described above, when the device is a positive quantum dot light-emitting diode (LED), after fabricating the electron transport layer, a cathode is deposited on the electron transport layer to obtain the LED. In some embodiments, before depositing the cathode, an electron injection layer is fabricated on the electron transport layer. When the device is an inverted quantum dot LED, after fabricating the electron transport layer, a two-point light-emitting layer is fabricated on the electron transport layer, and an anode is deposited on the quantum dot light-emitting layer to obtain the LED. In some embodiments, before depositing the anode, a hole functional layer is fabricated on the quantum dot light-emitting layer.

[0214] In this embodiment, the method for forming the hole functional layer (including at least one of the hole injection layer, hole transport layer and electron blocking layer) and the quantum dot light-emitting layer is preferably a solution processing method, including but not limited to one of spin coating, blade coating, printing, spraying, roller coating, electrodeposition, etc.

[0215] In the two embodiments described above, the prepared quantum dot light-emitting diodes are encapsulated. Encapsulation can be performed using conventional machine encapsulation or manually. Preferably, the oxygen and water content in the encapsulation environment is both below 0.1 ppm to ensure device stability. The curing resin used for encapsulation is an acrylic resin, an acrylate resin, or an epoxy resin; resin curing is achieved through UV irradiation, heating, or a combination of both.

[0216] In some embodiments, after the prepared quantum dot light-emitting diode is packaged according to the performance requirements of the quantum dot light-emitting diode device, the process further includes one or more treatments on the prepared quantum dot light-emitting diode, including ultraviolet irradiation, heating, positive and negative pressure, external electric field, and external magnetic field, to improve one or more aspects of the performance of the quantum dot light-emitting diode device. The atmosphere during the process can be air or an inert atmosphere.

[0217] The following description is based on specific embodiments.

[0218] Example 1

[0219] A quantum dot light-emitting diode (LED) includes an anode substrate and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, a hole transport layer disposed between the anode and the quantum dot light-emitting layer, a hole injection layer disposed between the anode and the hole transport layer, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The anode is ITO (55 nm), the hole injection layer is PEDOT:PSS (50 nm), the hole transport layer is TFB (30 nm), and the quantum dot light-emitting layer is red quantum dot Cd. x Zn 1-x The electron transport layer is a Se / ZnSe (40nm), the electron transport layer is a ZnO material (50nm) prepared by the following method, and the cathode is an Ag electrode (100nm).

[0220] The above-mentioned method for fabricating quantum dot light-emitting diodes includes:

[0221] A hole injection layer, a hole transport layer, and a quantum dot light-emitting layer are sequentially fabricated on an anode substrate;

[0222] Fabrication of an electron transport layer on a quantum dot luminescent layer;

[0223] Quantum dot light-emitting diodes are obtained by vapor deposition or sputtering of the top electrode onto a zinc oxide electron transport layer or a doped zinc oxide electron transport layer.

[0224] The method for preparing the electron transport layer is as follows:

[0225] (1) A) Dissolve zinc acetate dihydrate in dimethyl sulfoxide at room temperature to prepare a zinc salt solution with a concentration of 0.4 mol / L. Dissolve potassium hydroxide in isopropanol at room temperature to obtain an alkaline solution with a concentration of 0.7 mol / L. The molar ratio of hydroxide ions to zinc ions is 1.75:1.

[0226] (B) Adjust the temperature of the zinc salt solution to 40℃, and add the alkaline solution dropwise to the zinc salt solution according to the molar ratio of hydroxide ions to zinc ions of 1.75:1. Then add butylamine solution (0.4mol / L), wherein the amount of butylamine ligand added satisfies the following: the molar ratio of butylamine ligand to zinc salt in the zinc salt solution is 5:1. Keep the mixed solution stirred continuously at the reaction temperature of 40℃ for 120 min.

[0227] (C) After adding a precipitant with a volume ratio of 5:1 to the mixed solution after the reaction is completed, a white precipitate is produced in the mixed solution.

[0228] (D) Dissolve the obtained white precipitate to obtain a zinc oxide colloidal solution with a concentration of 0.6 mol / L;

[0229] (2) A zinc oxide colloidal solution is formed on the quantum dot light-emitting layer and dried at a temperature of 100°C to obtain a zinc oxide thin film with a thickness of 50 nm, i.e., an electron transport layer.

[0230] Comparative Example 1

[0231] The difference from Example 1 is that commercially available ordinary zinc oxide nanoparticles are used as the electron transport layer material.

[0232] The device lifetime test results of the quantum dot light-emitting diodes provided in Example 1 and Comparative Example 1 are as follows: Figure 8 As shown.

[0233] Example 2

[0234] A quantum dot light-emitting diode (LED) includes an anode substrate and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, a hole transport layer disposed between the anode and the quantum dot light-emitting layer, a hole injection layer disposed between the anode and the hole transport layer, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The anode is ITO (55 nm), the hole injection layer is PEDOT:PSS (50 nm), the hole transport layer is TFB (30 nm), and the quantum dot light-emitting layer is red quantum dot Cd. x Zn 1-x Se / ZnSe (40nm), the electron transport layer is ZnO material prepared by the following method, and the cathode is an Ag electrode (100nm).

[0235] The above-mentioned method for fabricating quantum dot light-emitting diodes includes:

[0236] A hole injection layer, a hole transport layer, and a quantum dot light-emitting layer are sequentially fabricated on an anode substrate;

[0237] Fabrication of an electron transport layer on a quantum dot luminescent layer;

[0238] Quantum dot light-emitting diodes are obtained by vapor deposition or sputtering of the top electrode onto a zinc oxide electron transport layer or a doped zinc oxide electron transport layer.

[0239] The method for preparing the electron transport layer is as follows:

[0240] (1) (A) Zinc acetate dihydrate was dissolved in dimethyl sulfoxide at room temperature to prepare a zinc salt solution with a concentration of 0.4 mol / L. Potassium hydroxide was dissolved in isopropanol at room temperature to obtain an alkaline solution with a concentration of 0.7 mol / L. The molar ratio of hydroxide ions to zinc ions was 1.75:1.

[0241] (B) Adjust the temperature of the zinc salt solution to 40℃, and add the alkaline solution dropwise to the zinc salt solution according to the molar ratio of hydroxide ions to zinc ions of 1.75:1. Then add butyric acid (0.4 mol / L) to the mixture. The amount of butyric acid ligand added is such that the molar ratio of butyric acid ligand to zinc salt in the zinc salt solution is 7:1. Keep the mixture stirred at 40℃ for 120 min.

[0242] (C) After adding a precipitant with a volume ratio of 5:1 to the mixed solution after the reaction is completed, a white precipitate is produced in the mixed solution.

[0243] (D) Dissolve the obtained white precipitate to obtain a zinc oxide colloidal solution with a concentration of 0.6 mol / L.

[0244] (2) A zinc oxide colloidal solution is formed on the quantum dot light-emitting layer and dried at a temperature of 100°C to obtain a zinc oxide thin film with a thickness of 50 nm, i.e., an electron transport layer.

[0245] The device lifetime test results of the quantum dot light-emitting diodes provided in Example 2 and Comparative Example 1 are as follows: Figure 9 As shown.

[0246] Example 3

[0247] A quantum dot light-emitting diode includes an anode substrate and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, a hole transport layer disposed between the anode and the quantum dot light-emitting layer, a hole injection layer disposed between the anode and the hole transport layer, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The anode is ITO (55 nm), the hole injection layer is PEDOT:PSS (50 nm), the hole transport layer is TFB (30 nm), the quantum dot light-emitting layer is red quantum dot CdxZn1-xSe / ZnSe (40 nm), the electron transport layer is ZnO material prepared by the following method, and the cathode is an Ag electrode (100 nm).

[0248] The above-mentioned method for fabricating quantum dot light-emitting diodes includes:

[0249] A hole injection layer, a hole transport layer, and a quantum dot light-emitting layer are sequentially fabricated on an anode substrate;

[0250] Fabrication of an electron transport layer on a quantum dot luminescent layer;

[0251] Quantum dot light-emitting diodes are obtained by vapor deposition or sputtering of the top electrode onto a zinc oxide electron transport layer or a doped zinc oxide electron transport layer.

[0252] The method for preparing the electron transport layer is as follows:

[0253] (1) (A) Zinc acetate dihydrate was dissolved in dimethyl sulfoxide at room temperature to prepare a zinc salt solution with a concentration of 0.5 mol / L. Potassium hydroxide was dissolved in isopropanol at room temperature to obtain an alkaline solution with a concentration of 0.9 mol / L. The molar ratio of hydroxide ions to zinc ions was 1.8:1.

[0254] (B) Adjust the temperature of the zinc salt solution to 40°C, and add the alkali solution dropwise to the zinc salt solution at a molar ratio of hydroxide ions to zinc ions of 1.8:1. Then, while maintaining the reaction temperature at 30°C, continue stirring the mixed solution for 80 minutes.

[0255] (C) After adding a precipitant with a volume ratio of 4:1 to the mixed solution after the reaction, a white precipitate is produced in the mixed solution.

[0256] (D) Dissolve the obtained white precipitate to obtain a zinc oxide colloidal solution with a concentration of 0.6 mol / L.

[0257] (2) A first zinc oxide colloidal solution is formed on the quantum dot light-emitting layer, the solvent is removed, and a zinc oxide pre-film is prepared. A propylamine solution (0.4 mol / L) is deposited on the surface of the zinc oxide pre-film, and the amount of ligand solution deposited and the weight of the lower zinc oxide pre-film are satisfied: for every 5 mg of zinc oxide pre-film, 25 μL of ligand solution is used for treatment, and the reaction is carried out at a temperature of 120 °C for 20 min. The solvent is removed, and a zinc oxide film with a thickness of 60 nm, i.e., an electron transport layer, is prepared.

[0258] The device lifetime test results of the quantum dot light-emitting diodes provided in Example 3 and Comparative Example 1 are as follows: Figure 10 As shown.

[0259] Example 4

[0260] A quantum dot light-emitting diode (LED) includes an anode substrate and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, a hole transport layer disposed between the anode and the quantum dot light-emitting layer, a hole injection layer disposed between the anode and the hole transport layer, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The anode is ITO (55 nm), the hole injection layer is PEDOT:PSS (50 nm), the hole transport layer is TFB (30 nm), and the quantum dot light-emitting layer is red quantum dot Cd. x Zn 1- xSe / ZnSe (40nm), the electron transport layer is ZnO material prepared by the following method, and the cathode is an Ag electrode (100nm).

[0261] The above-mentioned method for fabricating quantum dot light-emitting diodes includes:

[0262] A hole injection layer, a hole transport layer, and a quantum dot light-emitting layer are sequentially fabricated on an anode substrate;

[0263] Fabrication of an electron transport layer on a quantum dot luminescent layer;

[0264] Quantum dot light-emitting diodes are obtained by vapor deposition or sputtering of the top electrode onto a zinc oxide electron transport layer or a doped zinc oxide electron transport layer.

[0265] The method for preparing the electron transport layer is as follows:

[0266] (1) (A) Zinc acetate dihydrate was dissolved in dimethyl sulfoxide at room temperature to prepare a zinc salt solution with a concentration of 0.5 mol / L. Potassium hydroxide was dissolved in isopropanol at room temperature to obtain an alkaline solution with a concentration of 0.9 mol / L. The molar ratio of hydroxide ions to zinc ions was 1.8:1.

[0267] (B) Adjust the temperature of the zinc salt solution to 40°C, and add the alkali solution dropwise to the zinc salt solution at a molar ratio of hydroxide ions to zinc ions of 1.8:1. Then, while maintaining the reaction temperature at 30°C, continue stirring the mixed solution for 80 minutes.

[0268] (C) After adding a precipitant with a volume ratio of 4:1 to the mixed solution after the reaction, a white precipitate is produced in the mixed solution.

[0269] (D) Dissolve the obtained white precipitate to obtain a zinc oxide colloidal solution with a concentration of 0.6 mol / L;

[0270] (2) A first zinc oxide colloidal solution is formed on the quantum dot light-emitting layer, the solvent is removed, and a zinc oxide pre-film is prepared. A propionic acid solution (0.4 mol / L) is deposited on the surface of the zinc oxide pre-film, and the amount of ligand solution deposited and the weight of the lower zinc oxide pre-film are satisfied: for every 5 mg of zinc oxide pre-film, 25 μL of ligand solution is used for treatment, and the reaction is carried out at a temperature of 120 °C for 20 min. The solvent is removed, and a zinc oxide film with a thickness of 60 nm and an electron transport layer are prepared.

[0271] The device lifetime test results of the quantum dot light-emitting diodes provided in Example 4 and Comparative Example 1 are as follows: Figure 11 As shown.

[0272] The quantum dot light-emitting diodes provided in the above four embodiments and comparative examples were subjected to device lifetime performance testing using a QLED lifetime testing system. Specifically,

[0273] Model: New Vision NVO-QLED-LT-128

[0274] Working principle:

[0275] The 128-channel QLED lifespan testing system communicates via the PCI bus of the central processing computer, controlling the NI (National Instruments) digital I / O card to select the number of channels and output digital signals. The corresponding digital signals are converted into analog signals by a D / A chip to complete the current output (I), and data is acquired through a data acquisition card. Brightness is acquired by a sensor that converts light signals into electrical signals, using the electrical signals to simulate brightness changes (L).

[0276] Test method:

[0277] QLED Lifetime Testing Method (Constant Current Method)

[0278] (A) Select three to four different constant current densities (e.g., 100mA cm^2, 50mA cm^2, 20mA cm^2, 10mA cm^2) and test the initial brightness under the corresponding conditions.

[0279] (B) Maintain a constant current and record the changes in brightness and device voltage over time.

[0280] (C) Record the time it takes for the device to decay to T95, T80, T75, and T50 under different constant currents.

[0281] (D) Calculate the acceleration factor by curve fitting.

[0282] (E) Extrapolate the lifespan of devices T95, T80, T75, and T50 for 1000 nits using empirical formulas, as shown in Figure 12.

[0283] Calculation method: T T95@1000nits =(L MAX / 1000)^A*T 95

[0284] Where: L MAX -------Maximum brightness

[0285] A-------Acceleration Factor

[0286] T 95 ------The time it takes for the device's maximum brightness to decay to 95%.

[0287] The test results of the quantum dot light-emitting diodes provided in the four embodiments and comparative examples are shown in Table 2 below:

[0288] Table 2

[0289] sample Lifespan T95@1000nit(h) Example 1 893.45 Comparative Example 1 250.75 Example 2 1925.07 Example 3 865.11 Example 4 950.81

[0290] It should be understood that the test of the lifetime of quantum dot light-emitting diode devices is different from the characterization of the efficiency of quantum dot light-emitting diode devices. The device efficiency test time is usually short, so it characterizes the instantaneous state of the QLED device at the start of operation; while the device lifetime characterizes the ability of the device to maintain its efficiency after it has been working continuously and entered a steady state, that is, the balance of carrier injection in the device after entering a steady working state.

[0291] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for fabricating a quantum dot light-emitting diode, characterized in that, The quantum dot light-emitting diode includes an anode and a cathode disposed opposite to each other, a quantum dot light-emitting layer disposed between the anode and the cathode, and an electron transport layer disposed between the quantum dot light-emitting layer and the cathode. The electron transport layer includes a first electron transport layer containing zinc oxide, and at least the zinc oxide surface of the first electron transport layer contains amine ligands and / or carboxyl ligands having 3-7 carbon atoms. The method for preparing the first electron transport layer includes: A zinc oxide pre-film is prepared on the pre-fabricated device substrate on which the first electron transport layer is to be prepared; After depositing a solution of amine ligands and / or carboxyl ligands with 3-7 carbon atoms on the surface of the zinc oxide pre-film, the film is dried to obtain a zinc oxide film; wherein the amine ligands and / or carboxyl ligands with 3-7 carbon atoms are selected from at least one of propionic acid, propylamine, butyric acid, butylamine, hexanoic acid, and hexylamine.

2. The method for fabricating a quantum dot light-emitting diode as described in claim 1, characterized in that, The concentration of the amine ligand and / or carboxyl ligand solution having 3-7 carbon atoms is 0.05-0.5 mmol / L.

3. The method for fabricating a quantum dot light-emitting diode as described in claim 2, characterized in that, The amine ligands and / or carboxyl ligands having 3-7 carbon atoms have 3-4 carbon atoms, and the amount of amine ligands and / or carboxyl ligands having 3-7 carbon atoms added is such that: for every 5 mg of zinc oxide pre-made film, 100 μL-500 μL of amine ligands and / or carboxyl ligands having 3-7 carbon atoms are deposited.

4. The method for fabricating a quantum dot light-emitting diode as described in claim 2, characterized in that, The amine ligands and / or carboxyl ligands having 3-7 carbon atoms have 5-7 carbon atoms, and the amount of amine ligands and / or carboxyl ligands having 3-7 carbon atoms added satisfies the following: for every 5 mg of zinc oxide pre-made film, 50 μL-400 μL of amine ligands and / or carboxyl ligands having 3-7 carbon atoms are deposited.

5. The method for fabricating a quantum dot light-emitting diode as described in any one of claims 1 to 4, characterized in that, The drying process is carried out at a temperature of 10℃ to 100℃ for 10 minutes to 2 hours.

6. The method for fabricating a quantum dot light-emitting diode as described in any one of claims 1 to 4, characterized in that, The first electron transport layer is a metal-doped zinc oxide thin film.

7. The method for fabricating a quantum dot light-emitting diode as described in claim 6, characterized in that, The doped metal ions in the metal-doped zinc oxide thin film are selected from Mg. 2+ Mn 2+ At least one of them; or The doped metal ions in the metal-doped zinc oxide thin film are selected from Al. 3+ Y 3+ La 3+ Li + Gd 3+ Zr 4+ Ce 4+ At least one of them.

8. The method for fabricating a quantum dot light-emitting diode as described in claim 7, characterized in that, The doping concentration of the doped metal ions is as follows: When the doped metal ion is Mg 2+ At that time, Mg in the metal-doped zinc oxide thin film 2+ The molar content accounts for 0.1% to 35% of the total molar amount of metal ions; When the doped metal ion is Mn 2+ At that time, the Mn in the metal-doped zinc oxide thin film 2+ The molar content accounts for 0.1% to 30% of the total molar amount of metal ions; When the doped metal ion is Al 3+ At that time, the Al in the metal-doped zinc oxide thin film 3+ The molar content accounts for 0.1% to 15% of the total molar amount of metal ions; When the doped metal ion is Y 3+ At that time, the Y in the metal-doped zinc oxide thin film 3+ The molar content accounts for 0.1% to 10% of the total molar amount of metal ions; When the doped metal ion is La 3+ At that time, the La in the metal-doped zinc oxide thin film 3+ The molar content accounts for 0.1% to 7% of the total molar amount of metal ions; When the doped metal ion is Li + At that time, Li in the metal-doped zinc oxide thin film + The molar content accounts for 0.1% to 45% of the total molar amount of metal ions; When the doped metal ion is Gd 3+ At that time, Gd in the metal-doped zinc oxide thin film 3+ The molar content accounts for 0.01% to 8% of the total molar amount of metal ions; When the doped metal ion is Zr 4+ At that time, Zr in the metal-doped zinc oxide thin film 4+ The molar content accounts for 0.1% to 45% of the total molar amount of metal ions; When the doped metal ion is Ce 4+ At that time, Ce in the metal-doped zinc oxide thin film 4+ The molar content accounts for 0.1% to 10% of the total molar amount of metal ions.

9. The method for fabricating a quantum dot light-emitting diode as described in claim 8, characterized in that, The method for preparing the zinc oxide pre-film is as follows: Zinc oxide nanoparticles are prepared by mixing and reacting zinc salt solution with alkaline solution; zinc oxide nanoparticles are dissolved to obtain zinc oxide colloidal solution; zinc oxide colloidal solution is formed on the prefabricated device substrate, and the solvent is removed to obtain zinc oxide prefabricated film.

Citation Information

Patent Citations

  • Quantum dot surface ligand, and quantum dot film, preparation method and applications thereof

    CN109928903A

  • Composite thin film, and preparation method and application thereof

    CN109994629A

  • Quantum dot light emitting diode

    CN110890467A